A Comparison of Job Stress Models: Associations with Employee Well-Being, Absenteeism, Presenteeism, and Resulting Costs - Schmidt, Burkhard; Schneider, Michael; Seeger, Philipp; Van Vianen, Annelies; Loerbroks, Adrian; Herr, Raphael M. (Journal of Occupational and Environmental Medicine, 2019)
Objective:This study investigates the associations between Effort-Reward-Imbalance (ERI), Overcommitment (OC), Job-Demand-Control (JDC), and Organizational Injustice (OIJ) with employee well-being, absenteeism, and presenteeism, as well as the costs incurred.Methods:Cross-sectional data from 1440 German pharmaceutical company employees assessing job stress, employee well-being, absenteeism, and presenteeism were used. Linear regression and interval regression analyses assessed separate and independent associations and sample-specific costs were estimated.Results:All four stressors were related to employee well-being, presenteeism, and absenteeism when analyzed separately. OIJ showed the strongest independent association with absenteeism (coef. = 0.89; P < 0.01), whereas OC was most strongly independently associated with lower well-being (coef. = -0.44; P < 0.01) and higher presenteeism (coef. = 0.28; P < 0.01). Absenteeism costs per employee/year were higher than presenteeism costs.Conclusions:Occupational health interventions reducing job stress will have strong potential for productivity raise and lower costs.
CRIS-Team Scopus Importer:2022-11-28
Keywords: absenteeism; costs; job stress; presenteeism; well-being

Ambivalence in the Early Years of Marriage: Impact on Ambulatory Blood Pressure and Relationship Processes - Birmingham, Wendy C.; Wadsworth, Lori L.; Hung, Man; Li, Wei; Herr, Raphael M. (Annals of Behavioral Medicine, 2019)
Background: Marriage is associated with lower cardiovascular morbidity and mortality, but quality matters. Marriages characterized by ambivalent behaviors (containing both highly positive and highly negative behaviors concurrently) may not confer the same cardiovascular benefits as characterized by purely positive behavior. Ambivalence is assumed to take time to develop but couples in the early years of marriage may already exhibit ambivalent behaviors and thus be at increased risk for future cardiovascular events. Purpose: The purpose of this study was to determine the frequency of spouse and own ambivalent behavior, the impact on interpersonal (i.e., responsiveness, disclosure, affective interactions) processes, and ambulatory blood pressure (ABP) in individuals in the early years of marriage. Methods: In 84 young married couples, objective and subjective ambivalence, interpersonal functioning, and ABP over a 24-hr period were assessed. Results: As predicted, ambivalence developed early in marriage. Regarding interpersonal processes, spousal and own objective ambivalent behavior was associated with lower spousal responsiveness (p <. 01), disclosure (p <. 05), and more negative (p <. 03) and less positive interactions (p <. 001). Physiologically, ambivalent spousal behavior was associated with higher systolic blood pressure (p =. 02) and higher diastolic blood pressure (p =. 04). Measures of subjective ambivalence were congruent. Conclusions: Early marriages already contain ambivalent behavior; in such cases, individuals may not receive the cardiovascular protection of a supportive marriage.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Ambivalent; Blood pressure; Marriage; Partner responsiveness; Relationships

A sport focus of ECEC centres appears especially health-promoting for boys from lower socio-economic background - Mayer, A.; Herr, Raphael M.; Wiedemann, E.; Diehl, Katharina; Blume, M.; Hoffmann, S.; Jepsen, D.; Sundmacher, L.; Schneider, S. (EUROPEAN JOURNAL OF PUBLIC HEALTH, 2022)
CRIS-Team WoS Importer:2023-03-03

Association of adaptive and maladaptive narcissism with personal burnout: Findings from a cross-sectional study - Von Känel, Roland; Herr, Raphael M.; Van Vianen, Annelies Elizabeth Maria; Schmidt, Burkhard (Industrial Health, 2017)
Burnout is associated with poor mental and physical functioning and high costs for societies. Personality attributes may critically increase the risk of personal burnout. We specifically examined whether narcissism associates with personal burnout in a working population. We studied n=1,461 employees (mean age 41.3 ± 9.4 yr, 52% men) drawn from a random sample of a pharmaceutical company in Germany. All participants completed the personal burnout subscale of the Copenhagen Burnout Inventory and the Narcissistic Personality Inventory to assess maladaptive (entitlement/exploitativeness) and adaptive (leadership/authority) narcissism. In linear regression analysis, when mutually adjusting for the maladaptive and adaptive narcissism scales, higher adaptive narcissism was associated with lower burnout scores (ß = −0.04, p < 0.05), whereas higher maladaptive narcissism was associated with higher burnout scores (ß=0.04, p<0.05). Additionally, younger age (ß=−0.07), female gender (ß =0.11), depressive symptoms (ß =0.42), sleep problems (ß=0.30), stress at work (ß=0.23) and at home (ß = 0.09) were all independently associated with increased burnout scores (all p-values<0.01). Narcissistic personality attributes may play an important role in personal burnout. While maladaptive narcissism was associated with increased levels of burnout symptoms, adaptive narcissism was associated with fewer burnout symptoms.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Burnout; Fatigue; Narcissism; Personality; Psychiatric disorders; Psychosocial stress; Work environments

Associations between contextual and compositional characteristics of early childcare facilities with health, health behaviours and well-being among young children aged 06 years: Protocol for a scoping review - Hilger-Kolb, Jennifer; Schneider, Sven; Herr, Raphael M.; Osenbruegge, Nina; Hoffmann, Stephanie; Herke, Max; Pischke, Claudia; Sundmacher, Leonie; Diehl, Katharina (BMJ Open, 2020)
Introduction Early childhood is an important life stage which is crucial for determining health and health inequalities in later life. At the meso-level (institutional-level), early childcare facilities (eg, kindergartens, preschools) are the most important agent of socialisation next to families in young children aged 06 years. In recent years, an increasing amount of studies has focused on contextual and compositional characteristics of early childcare facilities and their association with health (eg, self-rated health), health behaviour (eg, physical activity) and well-being (eg, emotional well-being) in this age group. However, as currently no overview of the available literature on this topic exists, we will conduct a scoping review including various study designs (eg, cross-sectional studies, prospective studies, qualitative studies). Methods and analysis We will follow the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. A systematic search of the following scientific databases will be conducted: PubMed/Medline, PsycInfo, Sociological Abstracts, Education Resources Information Center and The Cochrane Library. During the selection process, we will follow a two-step process. First, two reviewers will independently screen titles/abstracts of all potentially eligible articles by applying a set of previously defined inclusion and exclusion criteria. After the completion of the title/abstract screening, full texts of the remaining articles will be screened following the same procedure. To determine inter-rater agreement between reviewers, we will calculate Cohen's Kappa after both steps. Key characteristics (eg, country of origin, sample size, study design) of included articles will be extracted. We will map the evidence available by providing a summary table on the key characteristics extracted and by presenting the associations using various types of illustrations. Ethics and dissemination Since no primary data will be collected for this review, ethical approval is not required. Our findings will be published in an international peer-reviewed journal and presented at national and international conferences.
CRIS-Team Scopus Importer:2021-12-06
Keywords: community child health; public health; social medicine

Associations Between Supportive Leadership and Employees Self-Rated Health in an Occupational Sample - Schmidt, Burkhard; Loerbroks, Adrian; Herr, Raphael M.; Wilson, Mark G.; Jarczok, Marc N.; Litaker, David; Mauss, Daniel; Bosch, Jos A.; Fischer, Joachim E. (International Journal of Behavioral Medicine, 2014)
Background: Protecting the health of the work force has become an important issue in public health research.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Leadership; Occupational Health; Self-rated health; Work stress; Workplace

Associations between Supportive Leadership Behavior and the Costs of Absenteeism and Presenteeism: An Epidemiological and Economic Approach - Schmid, Johannes Albert; Jarczok, Marc Nicolas; Sonntag, Diana; Herr, Raphael M.; Fischer, Joachim Ernst; Schmidt, Burkhard (Journal of Occupational and Environmental Medicine, 2017)
Objective: This study investigates associations between supportive leadership behavior (SLB) and presenteeism/absenteeism, and estimates related costs. Methods: Cross-sectional data from a German industrial sample (n = 17,060) assessing SLB and presenteeism/absenteeism were used. Adjusted interval regressions were performed. The study population was split into tertiles with respect to SLB, and minimum and maximum costs for each tertile were estimated on the basis of national industry averages. Results: Low SLB was associated with higher presenteeism [-0.31, 95% confidence interval (95% CI) -0.33 to -0.28)] and absenteeism (-0.36, 95% CI -0.40 to -0.32). Compared with high SLB, the costs of low SLB for absenteeism are between 534.54 and 1675.16 Euro higher per person and year. For presenteeism, this difference ranges between 63.76 and 433.7 Euro. Conclusions: SLB has the potential to reduce absenteeism, presenteeism, and associated costs. To contribute to workforce health, productivity, and efficiency, SLB merits being fostered by corporate policy.
CRIS-Team Scopus Importer:2022-11-28

Associations Between Work Characteristics, Engaged Well-Being at Work, and Job Attitudes — Findings from a Longitudinal German Study - Brokmeier, Luisa; Bosle, Catherin; Fischer, Joachim E.; Herr, Raphael M. (Safety and Health at Work, 2022)
Objective: The Job Demand & Resources model suggests work characteristics are related to mental well-being and work engagement. Previous work describes the development of a combined construct ‘engaged well-being at work’ (EWB). To what extent changes in measures of this construct are responsive to changes in job demands and resources or associated with changes in job-related attitudes has not been established. Methods: Longitudinal employee-level data from three waves (German Linked Personnel Panel) were used. Logistic and linear fixed effects regression analyses explored longitudinal associations between changes in EWB for participants over a three-year period with changes in job demands and resources and job-related attitudes (job commitment, satisfaction, and turnover intentions). Results: While job resources were associated with increased odds for a change into a healthier and/or more engaged category of EWB, job demands reduced them. Job resources were more strongly related to higher EWB (ORrange = 1.22 – 1.61) than job demands (ORrange = 0.79 – 0.96). Especially psychological job demands showed negative associations with improved EWB (OR = 0.79). A change from the least desirable category ‘disengaged strain’ to any other category of EWB was associated with greater odds by up to 20.6 % for increased commitment and job satisfaction and lower odds for turnover intentions. Discussion: Improving work characteristics, especially job resources, could increase employees' EWB, emphasizing the importance of job characteristics for a healthy workplace. Because EWB seems to be associated with job attitudes, an improvement of this indicator would be relevant for employees and employers.
Created from Fastlane, Scopus look-up
Keywords: Job attitudes; Job characteristics; Mental well-being; Work engagement; Workplace health

Associations between work stress and suicidal ideation: Individual-participant data from six cross-sectional studies - Loerbroks, Adrian; Cho, Sung-Il; Dollard, Maureen F.; Zou, Jianfang; Fischer, Joachim E.; Jiang, Yueying; Angerer, Peter; Herr, Raphael M.; Li, Jian (Journal of Psychosomatic Research, 2016)
Objective Epidemiological evidence suggests that work stress is associated with suicidal ideation (SI). However, only few studies in this area have drawn on well-established theoretical work stress models (i.e., the job-demand-control [JDC] model, the effort-reward-imbalance [ERI] model, and the model of organizational injustice [OJ]). Utilization of such models allows though for theory-based assessments and workplace interventions. Since evidence on those models' relationship with suicide-related outcomes is currently inconclusive (with regard to JDC), markedly sparse (OJ) or lacking (ERI), we aimed to provide additional or initial evidence. Methods We drew on original data from six cross-sectional studies, which were conducted in four countries (i.e., South Korea, China, Australia, and Germany). Work stress was measured by established questionnaires and was categorized into tertiles. In each study, SI was assessed by either one or two items taken from validated scales. Associations of work stress with SI were estimated for each study and were pooled across studies using multivariate random-effects logistic modeling. Results In the pooled analyses (n = 12,422) all three work stress models were significantly associated with SI with odds ratios fluctuating around 2. For instance, the pooled odds ratios for highest versus lowest work stress exposure in terms of job strain, OJ, and ERI equalled 1.91 (95% confidence interval [CI] = 1.52, 2.41), 1.98 (95% CI = 1.48, 2.65), and 2.77 (95% CI = 1.57, 4.88), respectively. Patterns of associations were largely consistent across the individual studies. Conclusion Our study provides robust evidence of a positive association between work stress and SI.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Effort-reward-imbalance; Job-demand-control; Organizational justice; Suicidal ideation; Work stress

Associations of ambivalent leadership with distress and cortisol secretion - Herr, Raphael M.; Van Harreveld, Frenk; Uchino, Bert N.; Birmingham, Wendy C.; Loerbroks, Adrian; Fischer, Joachim E.; Bosch, Jos A. (Journal of Behavioral Medicine, 2019)
Ambivalent social ties, i.e., whereby a relationship is evaluated simultaneously in positive and negative terms, are a potential source of distress and can perturb health-relevant biological functions. Social interactions at the workplace, in particular with supervisors, are often described in ambivalent terms, but the psychological and psychobiological impact of such interactions has received little scientific attention. The current study examined associations between ambivalent attitudes towards one’s supervisor, perceived distress (general and work-related), and diurnal dynamics of the stress hormone cortisol. 613 employees evaluated their supervisor in terms of positive and negative behaviors, which was combined into an ambivalent index. Higher ambivalence was associated with higher perceived distress and work-related stress (p <.001), and with a larger cortisol awakening response and higher day-time secretion post-awakening (p <.01). The present study is the first to identify ambivalence towards supervisors as a predictor of employee distress and stress-related endocrine dysregulation. In consequence, focusing solely on positive or negative leader behavior may insufficiently capture the true complexity of workplace interactions and attempts to compensate negative behaviors with positive are unlikely to reduce distress—but quite the opposite—by increasing ambivalence.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Ambivalence; Cortisol; Leadership; Stress; Supervisor

Associations of Changes in Organizational Justice with Job Attitudes and Health—Findings from a Prospective Study Using a Matching-Based Difference-in-Difference Approach - Herr, Raphael M.; Almer, Christian; Bosle, Catherin; Fischer, Joachim E. (International Journal of Behavioral Medicine, 2020)
Background: Ample evidence indicates that unfairness at the workplace (organizational injustice) is associated with both job attitudes and health of employees. Several factors that influence these associations have been identified: e.g., personality traits, such as the Big Five traits, justice sensitivity, type of occupation (e.g., white-collar), and unobserved time-invariant factors. Previous studies only addressed parts of these issues, and the ideal research design to mitigate biases—an experiment with random assignment to a treatment and control group—is not feasible. This study therefore mimics a randomized experiment using two statistical techniques. Methods: First, matching was implemented to balance the treatment and control group in confounding factors (demographics and personality) in two prospective waves (2012–2014) of observational data (4522 white-collar, 2984 blue-collar) taken from the Linked Personnel Panel, which is an employee survey representative for German private sector companies with more than 50 employees. Second, a difference-in-difference approach excludes unobserved time-invariant factors by estimating associations of changes in organizational justice (distributive, procedural, interactional) with job attitudes (job satisfaction, turnover intention) and health (general and mental) in these groups, separate for white- and blue-collar employees. Results: A decrease in perceived justice was associated with lower job attitudes (less job satisfaction and higher turnover intentions), while an increase was associated with higher values. This pattern was found for white- and blue-collar workers and also for health indicators, with the latter, however, being less pronounced. Conclusions: Increased fairness at the workplace is related to better job attitudes and health for white- and blue-collar employees, independent of personality traits and unobserved time-invariant factors.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Difference-in-difference; Health; Matching; Organizational justice; Personality; White and blue collar

Associations of individual factors and early childhood education and care (ECEC) centres characteristics with preschoolers’ BMI in Germany - Herr, Raphael M.; De Bock, Freia; Diehl, Katharina; Wiedemann, Eva; Sterdt, Elena; Blume, Miriam; Hoffmann, Stephanie; Herke, Max; Reuter, Marvin; Iashchenko, Iryna; Schneider, Sven (BMC Public Health, 2022)
Background: The number of obese children is rising worldwide. Many studies have investigated single determinants of children’s body mass index (BMI), yet studies measuring determinants at different potential levels of influence are sparse. The aim of this study is to investigate the independent role of parental socioeconomic position (SEP), additional family factors at the micro level, as well as early childhood education and care (ECEC) centre characteristics at the meso level regarding BMI. Methods: Analyses used the baseline data of the PReschool INtervention Study (PRINS) including up to 1,151 children from 53 ECEC centres. Multi-level models first estimated the associations of parental SEP indicators (parental school education, vocational training, and household income) with the children’s standard deviation scores for BMI (SDS BMI, standardised for age and gender). Second, structural (number of siblings), psychosocial (strained family relationships), and nutrition behavioural (soft-drink consumption, frequency of fast-food restaurant visits) family factors at the micro level were included. Third, characteristics of the ECEC centre at the meso level in terms of average group size, the ratio of overweight children in the group, ECEC centre type (all-day care), and the location of the ECEC centre (rural vs urban) were included. All analyses were stratified by gender and adjusted for age, migration background, and parental employment status. Results: Estimates for boys and girls appeared to differ. In the full model, for boys the parental SEP indicators were not related to SDS BMI. Factors related to SDS BMI in boys were: two or more siblings; B = -.55; p = 0.045 [ref.: no sibling]), the characteristics of the ECEC centre in terms of average group size (20 – 25 children; B = -.54; p = 0.022 [ref.: < 20 children]), and the ratio of overweight children (more overweight children B = -1.39; p < 0.001 [ref.: few overweight children]). For girls the number of siblings (two and more siblings; B =.67; p = 0.027 [ref.: no sibling]) and average group size (> 25 children; B = -.52; p = 0.037 [ref.: < 20 children]) were related to SDS BMI. Conclusions: The BMI of preschool children appears to be associated with determinants at the micro and meso level, however with some gender differences. The identified factors at the micro and meso level appear largely modifiable and can inform about possible interventions to reduce obesity in preschool children.
CRIS-Team Scopus Importer:2022-08-05
Keywords: BMI; ECEC centres; Kindergarten; Meso level; Obesity; Preschool children; Socioeconomic position

Associations of Organizational Justice with Tinnitus and the Mediating Role of Depressive Symptoms and Burnout—Findings from a Cross-Sectional Study - Herr, Raphael M.; Loerbroks, Adrian; Bosch, Jos A.; Seegel, Max; Schneider, Michael; Schmidt, Burkhard (International Journal of Behavioral Medicine, 2016)
Background: Tinnitus refers to the perception of a sound while an external source is absent. Research has identified work-related stress and its potential mental health-related sequelaes, i.e., depression and burnout, as risk factors for tinnitus. Perceived unfairness at work (organizational injustice), which is considered a psychosocial occupational stressor, has been shown to predict depression and burnout but its potential associations with tinnitus remains unaddressed. Purpose: The aim was to determine the relationship of organizational injustice with tinnitus, and to examine depression and burnout as potential mediators. Method: Cross-sectional data from a sample of 1632 employees were used. Tinnitus was assessed by self-report (n = 207; 13.9 %). Organizational justice and its subcomponents (interactional and procedural justice), burnout, and depressive symptoms were measured by validated questionnaires. Associations were assessed by logistic regressions, and mediation was assessed by maximum likelihood logistic regression estimations. Results: Overall organizational justice, interactional and procedural justice were inversely related to tinnitus (z-score for overall justice: OR = 0.754; 95 % CI = 0.649 to 0.876). These associations were independent of demographics, socioeconomic status, job characteristics (including potential noise exposure), and health behaviors. Mediation analyses suggested a potential mediation by burnout (95 % CI indirect effect −0.188 to −0.066) and depressive symptoms (95 % CI indirect effect −0.160 to −0.043). Parallel multiple mediation analysis revealed that mediation through burnout was significantly larger than through depressive symptoms. Conclusion: Organizational justice appeared inversely related to tinnitus and this association was explained by individual differences in burnout symptoms, suggesting mediation. Longitudinal studies may further help to strengthen the evidence base for prevention of tinnitus through promotion of organizational justice and prevention of burnout.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Burnout; Depressive symptoms; Mediation; Organizational justice; Tinnitus; Work stress

Associations of work stress with hair cortisol concentrations – initial findings from a prospective study - Herr, Raphael M.; Almer, Christian; Loerbroks, Adrian; Barrech, Amira; Elfantel, Irina; Siegrist, Johannes; Guendel, Harald; Angerer, Peter; Li, Jian (Psychoneuroendocrinology, 2018)
There is ample evidence supporting the link between stress at the workplace and physical and mental health. One of the pathways potentially mediating those associations may involve the hypothalamic-pituitary-adrenal (HPA) axis, with cortisol as an end product. While theoretically plausible, findings on the association of self-reported work stress with hair cortisol concentrations (HCC) are inconclusive, being potentially biased by omitted pertinent factors. This issue can be addressed, among others, by eliminating time-invariant factors through consideration of variation within persons over time. To this end, the present study examined the association between variation in HCC and perceived work stress − as assessed by the Effort-Reward-Imbalance (ERI) model − between two points in time (t1 and t2) over one year in a sample of 40 male factory workers. Neither a cross-sectional association, nor a link between change in ERI and HCC levels at t2 was observed. There was however a robust association of the change in ERI with the change of HCC. This effect was independent of baseline HCC and other confounders (Beta = 0.414, S.E. = 0.155, p = 0.012). Accordingly, this is the first study revealing prospective evidence for the associations of work stress with HCC, while excluding potentially time-stable confounding factors, like genetic factors or phenotypic hair color.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Change; Effort-reward imbalance; Hair cortisol; Repeated measurement; Time-invariant factors; Work stress

A systematic review of vitamin D status in populations worldwide - Hilger, Jennifer; Friedel, Angelika; Herr, Raphael M.; Rausch, Tamara; Roos, Franz; Wahl, Denys A.; Pierroz, Dominique D.; Weber, Peter; Hoffmann, Kristina (British Journal of Nutrition, 2014)
Vitamin D deficiency is associated with osteoporosis and is thought to increase the risk of cancer and CVD. Despite these numerous potential health effects, data on vitamin D status at the population level and within key subgroups are limited. The aims of the present study were to examine patterns of 25-hydroxyvitamin D (25(OH)D) levels worldwide and to assess differences by age, sex and region. In a systematic literature review using the Medline and EMBASE databases, we identified 195 studies conducted in forty-four countries involving more than 168000 participants. Mean population-level 25(OH)D values varied considerably across the studies (range 4·9-136·2nmol/l), with 37·3% of the studies reporting mean values below 50nmol/l. The highest 25(OH)D values were observed in North America. Although age-related differences were observed in the Asia/Pacific and Middle East/Africa regions, they were not observed elsewhere and sex-related differences were not observed in any region. Substantial heterogeneity between the studies precluded drawing conclusions on overall vitamin D status at the population level. Exploratory analyses, however, suggested that newborns and institutionalised elderly from several regions worldwide appeared to be at a generally higher risk of exhibiting lower 25(OH)D values. Substantial details on worldwide patterns of vitamin D status at the population level and within key subgroups are needed to inform public health policy development to reduce risk for potential health consequences of an inadequate vitamin D status. © 2013 The Authors.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Populations; Public health; Vitamin D

Autonomic nervous system activity and workplace stressors-A systematic review - Jarczok, Marc N.; Jarczok, Marion; Mauss, Daniel; Koenig, Julian; Li, Jian; Herr, Raphael M.; Thayer, Julian F. (Neuroscience and Biobehavioral Reviews, 2013)
Aim: This systematic review evaluates and summarizes the evidence of the association between psychosocial work environment as indicated by several work-stress models such as Job-Demand-Control (JDC), Effort-Reward-Imbalance (ERI), or Organizational Justice (OJ) and autonomic nervous system (ANS) function as indexed by heart rate variability (HRV). Method: We conducted a systematic literature search following the PRISMA-Statement in eleven databases including Medline, Web of Science and PsycINFO to address medical as well as psychological aspects of the relation between psychosocial work-stress models and HRV. Results: We identified 19 publications with a total of 8382 employees from ten countries reporting data from the years 1976-2008.Overall, nine of all studies report a negative and significant association between vagally-mediated HRV and measures of stress at work, while eight of all studies report a negative and significant association to mixed sympathetic and parasympathetic measures of HRV. Conclusions: This systematic review provides evidence that adverse psychosocial work conditions are negatively associated with ANS function as indexed by HRV. © 2013 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Employees; Heart rate variability; Psychosocial strain; Psychosocial work environment; Stress; Vagal tone

Bidirectional associations between psychological distress and hearing problems: an 18-year longitudinal analysis of the British Household Panel Survey - Herr, Raphael M.; Bosch, Jos A.; Theorell, Toeres; Loerbroks, Adrian (International Journal of Audiology, 2018)
Objective: Hearing problems are a significant public health concern. It has been suggested that psychological distress may represent both a cause and a consequence of hearing problems. Prospective data that allow testing such potential bi-directionality have thus far been lacking. The present study aimed to address this knowledge gap. Random (RE) and fixed effects (FE) panel regression models estimated the association of psychological distress (GHQ-12) and participant-reported hearing problems. Data from 18 annual waves of the British Household Panel Survey were used (n = 10,008). Psychological distress was prospectively associated with self-reported hearing problems in women (multivariable odds ratios (ORs) ≥1.44; one-year time lag ≥ 1.16) and men (ORs ≥ 1.15; time lag ≥ 1.17). Conversely, self-reported hearing problems were associated with increases in psychological distress in both sexes (OR ≥ 1.26; time lag ≥ 1.08). These associations were independent of the analytical strategy and of adjustment for sociodemographic variables, lifestyle factors, and measurement period. We present first evidence of a bidirectional association between psychological distress and self-reported hearing problems. These findings suggest that stress management interventions may contribute to the prevention of self-reported hearing problems, and, in turn, alleviating self-reported hearing problems may reduce psychological distress.
CRIS-Team Scopus Importer:2022-11-28
Keywords: cohort study; epidemiology; Hearing problems; psychological distress; self-report

Bipolar radiofrequency volumetric tissue reduction of the inferior turbinates: Evaluation of short-term efficacy in a prospective, randomized, single-blinded, placebo-controlled crossover trial - Bran, Gregor M.; Huennebeck, Sophia; Herr, Raphael M.; Hoermann, Karl; Stuck, Boris A. (European Archives of Oto-Rhino-Laryngology, 2013)
The objective of the study was to assess the short-term efficacy of radiofrequency volumetric tissue reduction (RFVTR) of the inferior turbinates in patients with nasal obstruction caused by turbinate hypertrophy. The study is a prospective, randomized, single-blinded, placebo-controlled, crossover trial. A total of 22 patients (age range 21-72 years; median age 41 years) were randomized into two treatment arms. Using a bipolar radiofrequency system, the first group (VP-group) received RFVTR (verum = V) first (at t1) followed by a placebo treatment (P) 6-8 weeks later (at t2). The PV-group was treated with placebo first at t1 and received RFVTR at t2. Subjects in both groups underwent identical procedures in an office-based setting. Delivery of radiofrequency energy was the only difference between the two groups. The outcome measures assessed were rhinomanometry, physician's evaluation of the degree of hypertrophy of the inferior turbinates and patients' estimation of nasal obstruction. Physician and patient evaluations were documented using a score ranging from 0 = none to 4 = severe. Evaluation was performed 6-8 weeks after every intervention. No intraoperative or postoperative complications occurred. Inferior turbinate hypertrophy improved significantly in both groups after RFVTR was performed (VP-group: p < 0.001; PV-group: p = 0.002). Nasal obstruction also decreased only after RFVTR (VP-group: p = 0.004, PV-group: p = 0.002). This study confirmed the safety of bipolar RFVTR as an office-based treatment of nasal obstruction due to inferior turbinate hypertrophy. We could prove that RFVTR is superior to placebo for reduction in turbinate hypertrophy and subjective improvement in nasal obstruction. To our knowledge, this is the first level I study proving the short-term efficacy of a bipolar radiofrequency system. Level of evidence 1b. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Crossover; Inferior turbinates; Nasal obstruction; Placebo-controlled; Radiofrequency volumetric tissue reduction

Cardiovascular and metabolic risk profile in german patients with moderate and severe psoriasis: A case control study - Warnecke, Christine; Manousaridis, Ioannis; Herr, Raphael M.; Terris, Darcey D.; Goebeler, Matthias; Goerdt, Sergij; Peitsch, Wiebke K. (European Journal of Dermatology, 2011)
Patients with psoriasis have a higher risk of cardiovascular and metabolic comorbidities, attributable to lifestyle factors, but also to shared inflammatory pathways and genetic factors. To investigate the association between moderate and severe psoriasis and metabolic and cardiovascular comorbidities, 100 patients hospitalized at University Medical Centre Mannheim, Germany, for psoriasis treatment were compared to two ageand sex-matched control groups, the first comprising other hospitalized patients (HCG) and the second comprising healthy individuals from an industrial cohort study (ICG). Multivariate logistic regression analysis with stepwise inclusion of cardiovascular risk factors was performed. Patients with psoriasis had significantly increased prevalences of smoking, obesity, diabetes, insulin resistance, pro-atherogenic cholesterol profiles and myocardial infarction and significantly decreased cardioprotective adiponectin. Unexpectedly, regression models controlling for confounding factors predicted significantly decreased OR for elevated total cholesterol in psoriasis cases (vs HCG: OR=0.50, p=0.045; vs ICG: OR=0.26, p=0.006). In contrast, OR for pro-atherogenic cholesterol profiles with LDL/HDL >3 was markedly increased (OR=2.45, p=0.012 or OR=3.02, p=0.020). Moreover, participants with psoriasis had significantly increased OR for elevated CRP as compared to the ICG (5.25, p=0.001). Our findings underscore the importance of cardiovascular and metabolic risk screening for all patients with moderate and severe psoriasis, including young patients.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Adiponectin; Cholesterol; Inflammation; Insulin resistance; Myocardial infarction; Psoriasis

Climate Change Worry in German University Students: Determinants and Associations with Health-Related Outcomes - Söder, Andrea; Herr, Raphael; Görig, Tatiana; Diehl, Katharina (Climate, 2025)
Climate change is known to have an impact on human health, including mental health. To better understand this phenomenon, the Climate Change Worry Scale (CCWS), a 10-item questionnaire, was developed to assess climate change worry as a psychological response to climate change. The aim of this study was to validate a German version of the CCWS among university students and to explore potential associations with health outcomes. The CCWS was translated into German and used in an online survey of 1105 university students. We tested the scale’s psychometric properties and assessed its associations with sociodemographic characteristics and health outcomes. These included the Somatic Symptom Scale-8, Jenkins Sleep Scale, WHO-5 Well-being Index, and Patient Health Questionnaire 8. All CCWS items loaded on one factor and the items showed high internal consistency. Positive associations were observed between climate change worry and self-reported somatic symptoms, sleep difficulties, mental well-being, and depressive symptoms in multivariate regression models. The German version of the CCWS is a valid tool to measure climate change worry and can be used in future studies. The association between the CCWS and mental health underscores the need to recognize that students perceive climate change as a serious threat.
CRIS-Team Scopus Importer:2025-03-07
Keywords: anxiety; climate change; Germany; mental health; students; university; worry

Correction: The longitudinal directional associations of meaningful work with mental well-being – initial findings from an exploratory investigation (BMC Psychology, (2023), 11, 1, (325), 10.1186/s40359-023-01308-x) - Herr, Raphael; Brokmeier, Luisa; Baron, Bertil N.; Mauss, Daniel; Fischer, Joachim E. (BMC Psychology, 2023)
Following publication of the original article [1], the authors brought two errors to the attention of the journal: panel 'c' was missing from Fig. 1; shared senior authorship of the last two authors, Daniel Mauss and Joachim E. Fischer, had been omitted from the author list. The article has since been updated to correct these errors, and the corrected figure and authorship can be seen in this erratum. The journal and the authors thank you for reading this erratum. (Figure presented.) Simplified illustration of reciprocal structural model between meaningful work (MfW) and mental well-being (MeWe). Panel A: total sample. Panel B: gender stratification. Panel C: stratification for white- (WC) and blue-collar (BC) employees. β = Standardized regression coefficients. Significant associations are in bold. Estimates based on the maximum likelihood method. Measurement errors were allowed to correlate to improve model fit
CRIS-Team Scopus Importer:2023-11-17

Co-stimulation with an olfactory stimulus increases arousal responses to trigeminal stimulation - Stuck, B. A.; Baja, J.; Lenz, F.; Herr, Raphael M.; Heiser, Clemens (Neuroscience, 2011)
An interaction of the intranasal chemical trigeminal and the olfactory system has previously been described. Intranasal chemical trigeminal stimulation during sleep leads to a dose-dependent increase in arousal reactions while pure olfactory stimuli are not able to trigger arousals or awakenings during sleep, regardless of the concentration used. The aim of the study was to assess whether co-stimulation with an olfactory substance increases arousal responses to intranasal chemical trigeminal stimulation. Experimental procedures: Five young healthy, normosmic volunteers of both sexes participated in the trial and 20 nights of testing were performed. For intranasal chemical trigeminal stimulation, CO2 was administered at 40% v/v and at 0% as a control stimulus. For olfactory co-stimulation, H2S was used at a concentration of 8 ppm. To compare the specific nasal chemical trigeminal/olfactory interaction with an interaction between an olfactory stimulus and peripheral somatosensory stimulation, an electrical stimulation protocol at the forearm was used with and without olfactory co-stimulation. Results: Chemical trigeminal stimulation with 40% CO2 led to an increase in arousal frequency compared to the control stimulus, which was most pronounced in light sleep. Co-stimulation with H2S was associated with higher arousal frequencies and shorter arousal latencies compared to isolated chemical trigeminal stimulation. The differences between the three study conditions were statistically significant for light sleep. Increasing electric stimulus concentration was associated with an increase in arousal frequency, again most pronounced in light sleep. Co-simulation with the olfactory stimulus did not lead to a systemic effect with regard to arousal reactions. Conclusions: The present results confirm the close interaction of the olfactory and chemical trigeminal system and support the idea that this interaction takes place at an early stage of processing. © 2011 IBRO.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Arousals; Chemosensation; Interaction; Olfaction; Trigeminal

Creating a measure to operationalize engaged well-being at work - Bosle, Catherin; Fischer, Joachim E.; Herr, Raphael M. (Journal of Occupational Medicine and Toxicology, 2021)
Background: Mental well-being and work engagement are both desirable, positive states of mind that help employees to better function in the workplace. While occupational researchers have argued in favor of considering both states concurrently, it is less clear how this might be translated to provide an instrument characterizing the workforce accordingly. The present study describes empirical efforts to operationalize a construct called engaged well-being. Methods: We used employee-level data (n = 13,538) from three waves of the German linked personnel panel (LPP; 2012–2017). Exploratory factor analysis and a combination of hierarchical and non-hierarchical cluster analyses linked with within-sum-of-squares statistics were used to identify distinct profiles describing mental well-being and work engagement concurrently. These profiles were then used as the basis to identify cut-offs to create replicable categories of engaged well-being. Using the longitudinal data from a subgroup providing data across more than one wave, we observed whether the newly constructed indicator changed over time. Results: The exploratory factor analysis suggested that both states were two distinct factors. Cluster analysis linked with within-sum-of-squares statistics suggested a four-cluster solution: engaged well-being (46.9%), disengaged well-being (27.5%), engaged strain (8.8%), and disengaged strain (16.8%). One cut-off for each state was identified to replicate the cluster solution. Across observation periods, we could observe changes in engaged well-being. Conclusions: Our measure of engaged well-being can be used to simultaneously characterize a workforce’s mental well-being and work engagement. Changes in this measure over time suggest its potential utility in organizational interventions. Future studies are needed to further explore both the antecedents, correlates, and potential effects of engaged well-being.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Cluster analysis; Employees; Mental well-being; Operationalization; Work engagement

Depression and inflammatory arthritis are associated in both Western and Non-Western countries: Findings from the World Health Survey 2002 - Apfelbacher, Christian; Brandstetter, Susanne; Herr, Raphael M.; Ehrenstein, Boris; Loerbroks, Adrian (Journal of Psychosomatic Research, 2017)
Objectives Epidemiological studies have linked arthritis to depression. However, it remains unclear to what degree the association between arthritis and depression extends to low income countries and whether it can be replicated for inflammatory arthritis (IA). We aimed to address these knowledge gaps based on a large multi-national sample. Methods Cross-sectional data was drawn from the 2002 World Health Survey. IA was defined as reports of either a diagnosis or treatment of arthritis and morning stiffness for > 30 min. Self-reported depression was defined as positive if participants reported its prior diagnosis or treatment or if they were classified as suffering from a major depressive episode by a seven-item screening instrument. Multivariable logistic regression analysis was used to estimate odds ratios (ORs) and 95% confidence intervals (CI) for the entire sample and stratified by sex and continent. Results The odds of IA was 2.6-fold increased in those with depression compared to those without (OR = 2.64, 95% CI 2.18–3.21) in the entire sample. This association was observed in both men (OR = 3.06, 95% CI 2.19–4.27) and women (OR = 2.50, 95% CI 1.95–3.21). Similar associations were found on the continent level, but were generally stronger for the Americas and Asia compared to Africa and Europe. Conclusions Although our definition of IA was limited by the use of self-reported morning stiffness, this study suggests that there is a positive association between inflammatory arthritis and depression in Western and Non-Western countries, suggesting that this relationship represents a universal phenomenon.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Comorbidity; Depression; Inflammatory arthritis; World Health Survey

Depression and smoking: Mediating role of vagal tone and inflammation - Taylor, Laine; Loerbroks, Adrian; Herr, Raphael M.; Lane, Richard D.; Fischer, Joachim E.; Thayer, Julian F. (Annals of Behavioral Medicine, 2011)
Background Depressed adults are more likely to become nicotine dependent and smokers are at increased risk for depression. Smoking and depression are each associated with inflammation and vagal tone. Purpose The purpose of this study is to determine as to what extent the association between depression and smoking is mediated by inflammation and/or vagal tone. Methods We studied a cross-sectional occupational sample (n=647) with information on the number of cigarettes smoked per day and depression (as measured by the Hospital Anxiety and Depression Scale). Heart rate variability, an indicator of vagal tone, was measured by electrocardiographic recordings. Inflammatory markers included C-reactive protein, white blood cells, and fibrinogen. Linear regression was employed along with the Freedman-Schatzkin test to assess mediation. Results We observed a positive association between depression and smoking (p<0.05). Vagal tone and fibrinogen were found to weakly attenuate this association. Conclusion These are the first data to demonstrate that the association between depression and smoking may partially be mediated by vagal tone and fibrinogen. © The Society of Behavioral Medicine 2011.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Depression; Heart rate variability; Inflammation; Smoking; Vagal tone; White blood cell count

Der UFair-Questionnaire: Messung der wahrgenommenen universitären Gerechtigkeit und ihr Zusammenhang mit der psychischen Gesundheit von Studierenden - Herr, Raphael; Deyerl, Veronika; Diehl, Katharina (Kooperationstagung der GMDS, DGSMP, DGEpi, DGMS und DGPH, 2024)

Die E-Zigarette als neuer Risikofaktor in der Jugendmedizin? - Huerkamp, Robert; Diehl, Katharina; Goerig, Tatiana; Herr, Raphael M.; Schneider, Sven (Kinder- und Jugendmedizin, 2016)
E-Zigaretten stellen ein neues gesundheitsrelevantes Phänomen – auch für die Kinder- und Jugendmedizin – dar. In der vorliegenden Studie haben wir ein Kollektiv deutscher Schülerinnen und Schüler nach Bekanntheit, Konsum und Risikoeinschätzung von E-Zigaretten befragt und die Ergebnisse geschlechtersensibel ausgewertet. Zwischen 10/2014 und 03/2015 wurden Daten von insgesamt 840 Schülerinnen und Schülern aus siebenten und achten Klassen der Metropolregion Rhein-Neckar anonym mittels eines standardisierten Fragebogens zu E-Zigaretten (einschließlich E-Shishas) erhoben. Obwohl die untersuchte Altersgruppe mit durchschnittlich 13 Jahren vergleichsweise jung ist, hatten bereits jede neunte Schülerin (12 %) und jeder fünfte Schüler (21 %) schon einmal E-Zigaretten konsumiert. Der Erstkonsum fand bei männlichen Schülern insgesamt früher statt. Wenn innerhalb der eigenen Familie oder der Peergroup E-Zigaretten benutzt wurden, griffen Jungen eher als Mädchen ebenfalls zur E-Zigarette. Im Vergleich zu Schülerinnen nahmen Schüler eher weniger potenzielle Risiken nikotinhaltiger E-Zigaretten wahr. Die Ergebnisse zeigen, dass viele Jugendliche E-Zigaretten zumindest schon einmal probiert haben, und legen geschlechtersensible Präventionsansätze nah

Die E–Zigarette – Verbreitung, Konsummuster und Nutzermotive bei Siebt- und Achtklässlern - Schneider, Sven; Herr, Raphael M.; Herth, Felix J.; Bauer-Kemény, Claudia; Huerkamp, Robert; Diehl, Katharina; Goerig, Tatiana (Sucht, 2016)
Objective: E-cigarettes are becoming increasingly popular worldwide. In this study we questioned a comparatively young group of German school pupils about their familiarity with e-cigarettes, their history of e-cigarette use, and their usage habits. We identified typical user groups and investigated their reasons for using e-cigarettes. Methods: As part of the PrevEND Study II, which is presented here for the first time, between 10/2014 and 03/2015 a total of 840 seventh- and eighth-grade school children from the Rheine-Neckar metropolitan region were anonymously asked standardized questions about e-cigarettes (including e-shishas). Results: Almost all of the pupils asked were familiar with e-cigarettes (98 %), and 16% had used an e-cigarette at least once. A social gradient became apparent in which 9 % of all "Gymnasium" (preparatory high school) students, 17% of "Realschule" (higher professional secondary school) students, and 33% of "Werkreal" and "Hauptschule"(lower professional secondary school) students had used an e-cigarette at least once (p < 0.001). The majority of e-cigarette users did not smoke tobacco products. E-cigarette use in a peer group was the most significant determinant of individual e-cigarette use. Additionally, the lifetime prevalence of e-cigarette use was higher than the lifetime prevalence of tobacco cigarette use. Conclusions: The results show that e-cigarette use is prevalent among adolescents and indicate the need for statewide monitoring and further investigation of this innovative product's risk profile.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Adolescents-motivation; E-cigarette; Electronic cigarette; Prevalence

Die Rolle von individuellen Faktoren und Kindergarten-Merkmalen in Bezug auf den BMI bei Kindergartenkindern - Herr, Raphael; Diehl, Katharina; Wiedemann, Eva; Mayer, Alena; Schneider, Sven (Kongress Armut und Gesundheit, 2022)

Dietary counselling for cardiovascular disease prevention in primary care settings: Results from a German physician survey - Goerig, Tatiana; Mayer, Manfred; Bock, Christina; Diehl, Katharina; Hilger, Jennifer; Herr, Raphael M.; Schneider, Sven (Family Practice, 2014)
Background: Primary care physicians (PCPs) play an important role in the promotion of healthy dietary behaviour. However, little is known about the practice of and factors associated with the provision of dietary counselling in primary health care in Germany. Objectives: To explore the attitudes towards and factors associated with the routine provision of dietary counselling in Germany using data from the nationwide, representative sample of the Physician Survey on Cardiovascular Disease Prevention. Methods: A total of 4074 randomly selected PCPs (response rate: 33.9%) provided data on dietary counselling for prevention of cardiovascular disease (CVD) based on the 5 A's (Assess, Advise, Agree, Assist, Arrange), attitudes towards dietary counselling and patients' and practice characteristics. Results: While the majority of PCPs (86%) reported having high levels of competence in providing dietary advice, only 49% felt they had been successful in counselling their patients on nutrition. PCPs routinely asked (68%) and advised patients to change their dietary habits more frequently (77%) compared to other counselling techniques based on the 5 A's. Female physicians and those with a higher percentage of privately insured patients and patients at higher risk of CVD were more likely to use the 5 A's to routinely counsel their patients on nutrition. Conclusions: The data showed high levels of involvement by German PCPs in CVD prevention and dietary counselling. The rather low perceived success of dietary intervention and differences with respect to patients' health insurance status indicate a need to address both communication skills in medical training and appropriate reimbursement of preventive services. ©The Author 2014. Published by Oxford University Press. All rights reserved.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Cardiovascular diseases; Counselling; Health behaviour; Physicians; Prevention; Primary health care

Differences in the Provision of Lifestyle Counseling for Cardiovascular Disease Prevention between Urban and Rural Regions in GermanyFindings from a National Survey of Primary Care Physicians Stadt-Land-Unterschiede im Angebot von Lebensstilberatung zur Prävention kardiovaskulärer Erkrankungen in der Hausarztpraxis. Ergebnisse einer bundesweiten Hausärztebefragung - Goerig, Tatiana; Diehl, Katharina; Herr, Raphael M.; Bock, C.; Mayer, M.; Schneider, S. (Gesundheitswesen, 2016)
Aims: In Germany, shortages in primary care physicians (PCPs) were reported in some rural regions. In this paper, we explored if regional differences in the distribution of PCPs are associated with the provision of lifestyle counseling in primary care. Methods: In a nationwide study, a total of 4,074 randomly selected PCPs were asked about provision of lifestyle counseling to their patients, their attitudes, and perceived barriers. Results: PCPs from rural regions provided less frequently lifestyle advice for cardiovascular disease prevention. Compared to their colleagues in urban areas, more PCPs from rural regions believed that were inadequately qualified for the lifestyle counseling and that they had been less successful in helping patients to modify their lifestyles. Physicians from rural practices named more often than PCPs from urban practices a lack of adherence by the patients (65 vs. 57%), insufficient opportunities to collaborate with providers of preventive services (62 vs. 55%), and lack of time (66 vs. 52%; all p<0.001) as barriers in providing patients with lifestyle counseling. Conclusion: Taking into account the expected increased shortages in PCPs in rural regions, the results show the need for targeted interventions for improving lifestyle counseling in rural practices.
CRIS-Team Scopus Importer:2021-12-06
Keywords: cardiovascular disease; lifestyle counseling; prevention; primary care physician

Drug survival in the treatment of generalized pustular psoriasis: A retrospective multicenter study - Kromer, Christian; Loewe, Emilia; Schaarschmidt, Marthe-Lisa; Pinter, Andreas; Gerdes, Sascha; Herr, Raphael M.; Poortinga, Sietske; Moessner, Rotraut; Wilsmann-Theis, Dagmar (Dermatologic Therapy, 2021)
Generalized pustular psoriasis (GPP) is a rare, potentially life-threatening inflammatory skin disease. Our aim was to assess patient and disease characteristics and analyze drug survival rates in the treatment of GPP in a real-life setting. In this retrospective study, 201 treatment series of 86 patients with GPP treated at five University Medical Centers were analyzed. Overall, excellent response was reached in 41.3% of all treatment courses, partial response in 31.4%, and nonresponse in 27.3%. Biological treatment was significantly more effective than non-biological therapies (excellent response: 47.4% vs 35.9%; P =.02). Overall, the median drug survival was 14.0 months (biologicals: 36.0 months vs nonbiologicals: 6.0 months; P <.001). The crude probability of survival was highest for secukinumab (hazard ratio [HR] of drug discontinuation compared with acitretin: 0.22), followed by ixekizumab and ustekinumab (HR: 0.38 each), adalimumab (HR: 0.59), etanercept (HR: 0.62), infliximab (HR: 0.69), cyclosporine (HR: 1.00), acitretin (reference for HR), fumaric acid esters (HR: 1.06), methotrexate (HR: 1.26), and apremilast (HR: 3.44); no drug discontinuation with guselkumab. Our results reveal high efficacy and drug survival, particularly for IL-17 and IL-(12)/23 antagonists. Thus, these biologics may be considered early in the therapeutic algorithm of GPP.
CRIS-Team Scopus Importer:2022-11-28
Keywords: GPP; IL-12/23; IL-17; TNF-alpha; Zumbusch

„Drug-Survival“-Raten und Gründe für den Abbruch von Systemtherapien bei Psoriasis - Arnold, Tobias; Schaarschmidt, Marthe Lisa; Herr, Raphael M.; Fischer, Joachim E.; Goerdt, Sergij; Peitsch, Wiebke K. (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Background and objectives: Moderate-to-severe psoriasis frequently requires long-term systemic therapy. Reflecting efficacy, safety, and treatment satisfaction, drug survival is an indicator of therapeutic success. The objective of the present study was to assess drug survival rates and reasons for discontinuation of fumaric acid esters (FAE), methotrexate (MTX), acitretin (ACI), cyclosporine A (CyA), adalimumab (ADA), etanercept (ETA), infliximab (INF), and ustekinumab (UST) in patients with moderate-to-severe psoriasis. Patients and methods: We performed a retrospective analysis of 373 patients who had received a total of 696 treatment courses at a German university hospital in the period 1/2003–5/2014. Results: The crude probability of survival was highest for UST, followed by ADA, ETA, INF, FAE, MTX, ACI, and CyA. In multivariate regression analysis using FAE as reference, hazard ratios (HR) for discontinuation were 0.14 (95 % confidence interval: 0.06– 0.35) for UST, 0.43 (0.26–0.73) for ADA, 2.11 (1.14–3.91) for ACI, and 3.26 (1.44–7.39) for CyA. INF showed longer survival when combined with MTX (HR 2.87, 1.21–6.81). Traditional systemic antipsoriatic agents as well as INF were most frequently discontinued due to adverse events; all other biologics, due to inefficacy with respect to cutaneous lesions. Conclusions: Drug survival rates should be integrated into therapeutic decisions in order to provide patients with an optimal long-term strategy.
CRIS-Team Scopus Importer:2022-11-28

Drug survival rates and reasons for drug discontinuation in patients with atopic dermatitis: a retrospective study of adult outpatients - Lopez, Jehane Pino; Kromer, Christian; Herr, Raphael M.; Schmieder, Astrid; Bayerl, Christiane; Schaarschmidt, Marthe-Lisa (European Journal of Dermatology, 2021)
Background: Treatment of moderate-to-severe atopic dermatitis (AD) can be challenging and little is known about the sustainability of on- and off-label prescribed systemic therapies. Objectives: To compare drug survival (DS) rates and reasons for drug discontinuation of cyclosporine A (CyA), dupilumab (DUP), azathioprine (AZA), methotrexate (MTX) and mycophenolate mofetil (MMF) prescribed under real-world conditions. Materials & Methods: In this retrospective study, 139 treatment courses for 94 adults with AD treated at two German dermatology departments were analysed. Results: Based on Cox regressions with CyA as reference category, hazard ratios for treatment discontinuation were 0.10 for DUP, 0.87 for MTX, 0.98 for MMF, and 1.18 for AZA. CyA, AZA, and MTX were most frequently interrupted due to adverse events, and MMF due to non-compliance. Only one patient (6.3%) discontinued DUP before the end of the observation period, which was due to ineffectiveness. Conclusion: Systemic therapies for AD differ with regards to DS and reasons leading to treatment withdrawal; this should be considered in real-life practice.
CRIS-Team Scopus Importer:2022-11-28
Keywords: atopic dermatitis; drug survival; maintenance rate; systemic treatment; treatment discontinuation

Drug survival rates and reasons for drug discontinuation in psoriasis - Arnold, Tobias; Schaarschmidt, Marthe-Lisa; Herr, Raphael M.; Fischer, Joachim E.; Goerdt, Sergij; Peitsch, Wiebke K. (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Background and objectives: Moderate-to-severe psoriasis frequently requires longterm systemic therapy. Reflecting efficacy, safety, and treatment satisfaction, drug survival is an indicator of therapeutic success. The objective of the present study was to assess drug survival rates and reasons for discontinuation of fumaric acid esters (FAE), methotrexate (MTX), acitretin (ACI), cyclosporine A (CyA), adalimumab (ADA), etanercept (ETA), infliximab (INF), and ustekinumab (UST) in patients with moderate-to-severe psoriasis. Patients and methods: We performed a retrospective analysis of 373 patients who had received a total of 696 treatment courses at a German university hospital in the period 1/2003–5/2014. Results: The crude probability of survival was highest for UST, followed by ADA, ETA, INF, FAE, MTX, ACI, and CyA. In multivariate regression analysis using FAE as reference, hazard ratios (HR) for discontinuation were 0.14 (95 % confidence interval: 0.06– 0.35) for UST, 0.43 (0.26–0.73) for ADA, 2.11 (1.14–3.91) for ACI, and 3.26 (1.44–7.39) for CyA. INF showed longer survival when combined with MTX (HR 2.87, 1.21–6.81). Traditional systemic antipsoriatic agents as well as INF were most frequently discontinued due to adverse events; all other biologics, due to inefficacy with respect to cutaneous lesions. Conclusions: Drug survival rates should be integrated into therapeutic decisions in order to provide patients with an optimal long-term strategy.
CRIS-Team Scopus Importer:2022-11-28

Effect of a disease-monitoring smartphone application in combination with a patient educational program on mental health of patients with psoriasis: A randomized intervention study - Beck, Alena; Schulze-Hagen, Theresa; Domogalla, Lena; Herr, Raphael M.; Benecke, Johannes; Schmieder, Astrid (Journal of the American Academy of Dermatology, 2021)
CRIS-Team Scopus Importer:2022-11-28

Effects and mediators of psychosocial work characteristics on somatic symptoms six years later: Prospective findings from the Mannheim Industrial Cohort Studies (MICS) - Herr, Raphael M.; Li, Jian; Loerbroks, Adrian; Angerer, Peter; Siegrist, Johannes; Fischer, Joachim E. (Journal of Psychosomatic Research, 2017)
Objective Ample evidence documented the adverse health effects of work stressors, and recent research has increasingly focused on somatic symptoms which are very common and costly. Prospective evidence is however sparse and yielded mixed findings. Furthermore, there is reason to assume that depression and anxiety might mediate the effects of adverse psychosocial work conditions on somatic symptoms. This study aimed to investigate longitudinal effects of work stressors on somatic symptoms and the potential mediation by anxiety and/or depression. Methods Six year follow-up data from 352 individuals – free of potentially stress-related chronic disease – were utilized. Somatic symptoms were assessed by 19 items of an established list of complaints at baseline and follow-up. The effort-reward-imbalance (ERI) model measured adverse psychosocial work conditions and over-commitment (OC). Linear regressions adjusted for socio-demographics, social status, lifestyle, and baseline symptoms estimated the effects of the ERI ratio, effort, reward, OC, and the ERI ratio × OC interaction on somatic symptoms six years later. Furthermore, single and multiple mediation by anxiety and/or depression was investigated. Results There was a strong longitudinal effect of the ERI ratio, as well as of its subcomponents, and OC on somatic symptoms (all Bs ≥ | 0.49 |; p-values ≤ 0.004). Moreover, the ERI ratio × OC interaction was significant (p-value = 0.047). Multiple mediation analyses revealed especially anxiety to mediate the effect of work stressors on somatic symptoms (Sobel test = 0.007). Conclusion Adverse psychosocial work conditions seem to longitudinally affect somatic symptoms, potentially moderated by OC, and mediated by anxiety.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Cohort study; Effort-reward imbalance; Mental health; Psychosocial work characteristics; Somatic symptoms

Effects of an artificial smoke on arousals during human sleep - Heiser, Clemens; Baja, J.; Lenz, F.; Sommer, J. U.; Hoermann, K.; Herr, Raphael M.; Stuck, B. A. (Chemosensory Perception, 2012)
The central processing of olfactory stimuli is different compared to other sensory systems, as they are not followed by arousals at least with regard to pure olfactory substances such as hydrogen sulfite. It is still unclear, however, whether a stimulus with a higher significance to the sleeper increases arousal frequency. Fifteen healthy volunteers participated in this controlled trial. Intranasal chemosensory stimulation was performed during sleep with an olfactometer. Artificial smoke was selected as an olfactory stimulus with high significance for different stimulus durations (1, 5, and 20 s), and carbon dioxide (CO2) was used in a concentration of 40 % v/v for isolated trigeminal stimulation as an internal control. Arousal reactions in relation to chemosensory stimulation during sleep were assessed with the help of overnight sleep recordings during 30 nights of testing. Stimulation with an artificial smoke did not increase arousal frequency. In contrast, stimulation with CO 2 leads to an increase in arousal frequency. Even for the longest stimulus duration of artificial smoke, a statistically significant increase in arousal frequency could not be detected. Even a strong and significant olfactory stimulus such as artificial smoke does not elicit arousals during human sleep. Overall, the results confirm the unique role of the olfactory system in sensory physiology. © Springer Science+Business Media, LLC 2012.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Arousals; Chemosensation; CO; Olfaction; Sleep; Smoke

Effects of psychosocial work characteristics on hair cortisol–findings from a post-trial study - Herr, Raphael M.; Barrech, Amira; Guendel, Harald; Lang, Jessica; Quinete, Natalia Soares; Angerer, Peter; Li, Jian (Stress. The International Journal on the Biology of Stress, 2017)
Prolonged work stress, as indicated by the effort-reward imbalance (ERI) model, jeopardizes health. Cortisol represents a candidate mechanism connecting stress to ill health. However, previous findings appear inconclusive, and recommendations were made to assess work stress at multiple time points and also to investigate ERI (sub-)components. This study therefore examines the effects of two single time points, as well as the mean and change scores between time points of ERI and its components on hair cortisol concentration (HCC), a long-term cortisol measurement. Participants were 66 male factory workers (age: 40.68 ± 6.74 years; HCC: 9.00 ± 7.11 pg/mg), who were followed up after a stress management intervention (2006–2008). In 2008 (T1) and 2015 (T2), participants completed a 23-item ERI questionnaire, assessing effort, the three reward components (esteem, job security, job promotion) and over-commitment. In 2015, participants also provided a 3-cm hair segment close to the scalp for HCC analysis, as well as information on relevant confounders (i.e. medication intake, age, work characteristics, socioeconomic and lifestyle factors, number of stressful life events). Linear regressions revealed hardly any cross-sectional or longitudinal effect of ERI and its components on HCC. Only the change scores between T1 and T2 of job security were negatively associated with lower HCC in unadjusted (β = −.320; p =.009) and adjusted (β = −.288; p =.044) models. In this study, only a decrease of perceived job security over time was significantly associated with higher HCC, and other predictors were not related to this outcome. Especially after correction for multiple testing, this study revealed just a weak association of different psychosocial work measurements with HCC. Lay summary This study showed that an increase in perceived job insecurity is correlated with higher levels of the stress hormone cortisol. The higher levels of cortisol might represent a biological explanation for the negative health effects of job insecurity. The association was, however, relatively low, and more and more voices are questioning whether cortisol in hair is a reliable marker for perceived work stress.
CRIS-Team Scopus Importer:2022-11-28
Keywords: change; effort-reward imbalance; hair cortisol; job security; longitudinal; Work stress

Effort-reward imbalance among students at German universities: associations with self-rated health and mental health - Hilger-Kolb, Jennifer; Diehl, Katharina; Herr, Raphael M.; Loerbroks, Adrian (International Archives of Occupational and Environmental Health, 2018)
Purpose: Although psychosocial stress has been associated with adverse health parameters, little is known about this topic among the variety of university students. We thus examined associations of psychosocial stress due to academic education with self-rated health, and symptoms of depression and anxiety among students from various study disciplines. Methods: We used data from the Nutrition and Physical Activity (NuPhA) Study, a cross-sectional online survey among students enrolled across German universities (n = 698). Academic stress was assessed by a newly developed and validated student version of the Effort–Reward Imbalance (ERI-Student) Questionnaire. Depressive and anxiety symptoms were measured by applying the Patient Health Questionnaire-4 (PHQ-4) and using validated cut-offs. Results: Separate multivariate logistic regression analyses run for the different ERI components, the ERI-ratio revealed that high effort, low reward, high over-commitment, and a high ERI-ratio were associated with poor self-rated health, and depressive and anxiety symptoms (odds ratios ≥ 2.43). Separate analyses for medical students and non-medical students largely confirmed these findings for both groups. Associations between all ERI components, the ERI ratio, and both mental health measures were, however, more pronounced among medical students. Conclusions: We were able to show consistent associations between the ERI-Student Questionnaire and self-rated health and mental health across students from different study disciplines. Further research on associations between academic stress and health parameters is necessary to develop effective strategies that prevent students from adverse health outcomes during their academic education.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Effort-reward imbalance; Mental health; Psychosocial stress; Self-rated health; University students

Effort-reward imbalance is associated with the metabolic syndrome - Findings from the Mannheim Industrial Cohort Study (MICS) - Schmidt, Burkhard; Bosch, Jos A.; Jarczok, Marc N.; Herr, Raphael M.; Loerbroks, Adrian; Van Vianen, Annelies E. M.; Fischer, Joachim E. (International Journal of Cardiology, 2015)
Background/objectives Job stress is a predictor of cardiovascular disease incidence and mortality and the metabolic syndrome (MetS) represents one of the key pathways potentially underlying those associations. Effort-reward imbalance (ERI) represents one of the most influential theoretical work stress models, but evidence on its relationship with MetS remains sparse and with only limited generalizability. We therefore aimed to determine this association in a large occupational sample with different occupational groups.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Effort; Effort-reward imbalance; Job stress; Metabolic syndrome; Reward; Workplace

Elevated HbA1c levels and the accumulation of differentiated T cells in CMV+ individuals - Rector, Jerrald L.; Thomas, G. Neil; Burns, Victoria E.; Dowd, Jennifer B.; Herr, Raphael M.; Moss, Paul A.; Jarczok, Marc N.; Hoffman, Kristina; Fischer, Joachim E.; Bosch, Jos A. (Diabetologia, 2015)
Aims/hypothesis: Biological ageing of the immune system, or immunosenescence, predicts poor health and increased mortality. A hallmark of immunosenescence is the accumulation of differentiated cytotoxic T cells (CD27−CD45RA+/−; or dCTLs), partially driven by infection with the cytomegalovirus (CMV). Immune impairments reminiscent of immunosenescence are also observed in hyperglycaemia, and in vitro studies have illustrated mechanisms by which elevated glucose can lead to increased dCTLs. This study explored associations between glucose dysregulation and markers of immunosenescence in CMV+ and CMV− individuals. Methods: A cross-sectional sample of participants from an occupational cohort study (n = 1,103, mean age 40 years, 88% male) were assessed for HbA1c and fasting glucose levels, diabetes, cardiovascular risk factors (e.g. lipids), numbers of circulating effector memory (EM; CD27−CD45RA−) and CD45RA re-expressing effector memory (EMRA; CD27−CD45RA+) T cells, and CMV infection status. Self-report and physical examination assessed anthropometric, sociodemographic and lifestyle factors. Results: Among CMV+ individuals (n = 400), elevated HbA1c was associated with increased numbers of EM (B = 2.75, p < 0.01) and EMRA (B = 2.90, p < 0.01) T cells, which was robust to adjustment for age, sex, sociodemographic variables and lifestyle factors. Elevated EM T cells were also positively associated with total cholesterol (B = 0.04, p < 0.05) after applying similar adjustments. No associations were observed in CMV− individuals. Conclusions/interpretation: The present study identified consistent associations of unfavourable glucose and lipid profiles with accumulation of dCTLs in CMV+ individuals. These results provide evidence that the impact of metabolic risk factors on immunity and health can be co-determined by infectious factors, and provide a novel pathway linking metabolic risk factors with accelerated immunosenescence.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Cholesterol; CMV; Cytomegalovirus; Diabetes; Glucose; Haemoglobin A; HbA; Immune ageing; Metabolic syndrome; T cell

Health inequalities in children and adolescents: A scoping review of the mediating and moderating effects of family characteristics - Blume, Miriam; Rattay, Petra; Hoffmann, Stephanie; Spallek, Jacob; Sander, Lydia; Herr, Raphael M.; Richter, Matthias; Moor, Irene; Dragano, Nico; Pischke, Claudia; Iashchenko, Iryna; Hoevener, Claudia; et al. (International Journal of Environmental Research and Public Health, 2021)
This scoping review systematically mapped evidence of the mediating and moderating effects of family characteristics on health inequalities in school-aged children and adolescents (6–18 years) in countries with developed economies in Europe and North America. We conducted a systematic scoping review following the PRISMA extension for Scoping Reviews recommendations. We searched the PubMed, PsycINFO and Scopus databases. Two reviewers independently screened titles, abstracts and full texts. Evidence was synthesized narratively. Of the 12,403 records initially identified, 50 articles were included in the synthesis. The included studies were conducted in the United States (n = 27), Europe (n = 18), Canada (n = 3), or in multiple countries combined (n = 2). We found that mental health was the most frequently assessed health outcome. The included studies reported that different family characteristics mediated or moderated health inequalities. Parental mental health, parenting practices, and parent-child-relationships were most frequently examined, and were found to be important mediating or moderating factors. In addition, family conflict and distress were relevant family characteristics. Future research should integrate additional health outcomes besides mental health, and attempt to integrate the complexity of families. The family characteristics identified in this review represent potential starting points for reducing health inequalities in childhood and adolescence.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Family conflict; Health; Health behavior; Health inequalities; Mediation; Moderation; Parent-child relationship; School-age parenting; Socioeconomic position

Higher levels of psychological distress are associated with a higher risk of incident diabetes during 18 year follow-up: Results from the British household panel survey - Mommersteeg, Paula M. C.; Herr, Raphael M.; Zijlstra, Wobbe P.; Schneider, Sven; Pouwer, Francois (BMC Public Health, 2012)
Background: Reviews have shown that depression is a risk factor for the development of type 2 diabetes. However, there is limited evidence for general psychological distress to be associated with incident diabetes. The aim of the present study was to test whether persons who report higher levels of psychological distress are at increased risk to develop type 2 diabetes during 18 years follow up, adjusted for confounders. Methods. A prospective analysis using data from 9,514 participants (41 years, SD=14; 44% men) of the British Household Panel Survey. The General Health Questionnaire 12 item version was used to assess general psychological distress, diabetes was measured by means of self-report. Cox proportional hazards regression models were used to calculate the multivariate-adjusted hazard ratio (HR) of incident diabetes during 18 years follow up, comparing participants with low versus high psychological distress at baseline (1991). Results: A total of 472 participants developed diabetes 18 year follow up. Those with a high level of psychological distress had a 33% higher hazard of developing diabetes (HR=1.33, 95% CI 1.10-1.61), relative to those with a low level of psychological distress, adjusted for age, sex, education level and household income. After further adjustment for differences in level of energy, health status, health problems and activity level, higher psychological distress was no longer associated with incident diabetes (HR=1.10, 95% CI 0.91-1.34). Conclusions: Higher levels of psychological distress are a risk factor for the development of diabetes during an 18 year follow up period. This association may be potentially mediated by low energy level and impaired health status. © 2012 Mommersteeg et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2022-11-28
Keywords: British household panel survey; Prospective; Psychological distress; Risk factor; Type 2 diabetes

Household air pollution and angina pectoris in low-and middle-income countries: Cross-sectional evidence from the world health survey 2002–2003 - Tiwari, Ishwar; Herr, Raphael M.; Loerbroks, Adrian; Yamamoto, Shelby S. (International Journal of Environmental Research and Public Health, 2020)
The evidence regarding the effects of household air pollution on angina pectoris is limited in low-and middle-income countries (LMICs). We sought to examine the association between household air pollution and angina pectoris across several countries. We analyzed data of individuals from 46 selected countries participating in the cross-sectional World Health Survey (WHS) 2002–2003. Pooled and stratified (sex, continent) logistic regression with sampling weights was used to estimate adjusted odds ratios (ORs) and 95% confidence intervals (CIs) to quantify associations between the use of different household fuels with angina pectoris. In the pooled sample, we observed lower odds of angina pectoris with electricity use (OR: 0.68, 95% CI: 0.56–0.83) compared to those households reporting the use of gas as a household fuel. Increased odds of angina pectoris were observed with the use of agriculture/dung/shrub/other (OR: 1.65, 95% CI: 1.30–2.09), mixed (solid and non-solid fuels) (OR: 1.31, 95% CI: 1.09–1.56), and mixed solid fuel use (OR: 1.59, 95% CI: 1.12–2.25). Higher odds of angina pectoris were observed mainly with solid fuel use. The results highlight the importance of addressing these issues, especially in regions with a high proportion of solid fuel users and increasing levels of cardiovascular disease.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Angina; Angina pectoris; Chest-pain; Household air pollution; Solid fuel

Impact of an eHealth smartphone app on the mental health of patients with psoriasis: Prospective randomized controlled intervention study - Domogalla, Lena; Beck, Alena; Schulze-Hagen, Theresa; Herr, Raphael M.; Benecke, Johannes; Schmieder, Astrid (JMIR mHealth and uHealth, 2021)
Background: Psoriasis has a negative impact on patients' physical and mental health and can lead to anxiety and depression. Disease management strategies, including educational programs and eHealth devices, have been shown to improve health care for several chronic diseases. However, such disease management strategies are lacking in the routine care of patients with psoriasis. Objective: This study aims to study the impact of a novel intervention that combines an educational program with a disease management smartphone app on the mental health of patients with psoriasis. Methods: Patients with psoriasis in the intervention group received an educational program; attended visits on weeks 0, 12, 24, 36, and 60; and had access to the study app. Patients in the control group only attended the visits. The primary endpoint was a significant reduction of scores on the Hospital Anxiety and Depression Scale (HADS). Secondary end points were reductions in Dermatology Life Quality Index score, Psoriasis Area and Severity Index score, pruritus, and pain, as well as improvements in mood and daily activities. In addition, modulating effects of sex, age, disease duration, and app use frequency were evaluated. Results: A total of 107 patients were included in the study and randomized into the control group (53/107, 49.5%) or intervention group (54/107, 50.5%). Approximately 71.9% (77/107) of the patients completed the study. A significant reduction in HADS-Depression (HADS-D) in the intervention group was found at weeks 12 (P=.04) and 24 (P=.005) but not at weeks 36 (P=.12) and 60 (P=.32). Patient stratification according to app use frequency showed a significant improvement in HADS-D score at weeks 36 (P=.004) and 60 (P=.04) and in HADS-Anxiety (HADS-A) score at weeks 36 (P=.04) and 60 (P=.05) in the group using the app less than once every 5 weeks. However, in patients using the app more than once every 5 weeks, no significant reduction in HADS-D (P=.84) or HADS-A (P=.20) score was observed over the 60-week study period compared with that observed in patients in the control group. All findings were independent of sex, age, and disease duration. Conclusions: These findings support the use of a disease management smartphone app as a valid tool to achieve long-term improvement in the mental health of patients with psoriasis if it is not used too frequently. Further studies are needed to analyze the newly observed influence of app use frequency.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Disease management; EHealth; Mental health; MHealth; Mobile phone; Patient educational program; Psoriasis; Smartphone app; Teledermatology; Telemedicine

Improving Outcomes and Quality of Life for Patients With Hand and Foot Eczema: Randomized Study of a Patient-Centered Monitoring App - Bruch, Aimee; Weigandt, Wanja; Schardt, Yannic; Herr, Raphael; Benecke, Johannes; Schmieder, Astrid (Journal of Medical Internet Research, 2025)
Background: Hand and foot eczema is a frequent chronic dermatological condition. The persistent itching, pain, and blistering can impair hand and foot function, leading to difficulties in performing tasks requiring fine motor skills. In addition, the impact on the quality of life for affected patients is significant, as the symptoms can be extremely uncomfortable and disruptive to daily activities. By incorporating digital health apps and educational programs into the management of hand and foot eczema, patients may receive ongoing support, optimize their clinical outcomes, and ultimately enhance their overall quality of life. Objective: The purpose of this study was to evaluate the effect of a smartphone app combined with educational training on the clinical outcomes and mental health of patients with chronic hand and foot eczema during a 60-week study period. Methods: Patients in the intervention group participated in an educational program focused on chronic hand and foot eczema at baseline and had in-person visits at weeks 0, 12, 24, 36, and 60, as well as access to our study smartphone app. The app allowed patients to upload pictures of their hands and feet and answer questions about pain severity, itching, mood, and quality of life. A chat function was also available for patients to contact their dermatologist. The control group received only the in-person study visits described above. Results: A total of 87 patients were included in the study and randomized to the intervention (n=43) or control (n=44) groups. In total, 23 patients from the intervention group and 34 patients from the control group completed the study. Throughout the 60-week study period, a significant reduction in Hand Eczema Severity Index (HECSI) was consistently observed in all patients (week 60: linear regression coefficient [Coef]=–1.108; P≤.001). A trend toward a greater improvement of the HECSI in the intervention group compared to the control group was noticed (week 60: Coef=0.597; P=.05). Subgroup analysis revealed that patients who used the app with a usage frequency of less than 20% demonstrated a significant reduction in the HECSI from week 0 to week 60 (week 60: Coef=–1.275; P=.04) and a significant reduction in the Dermatology Life Quality Index (week 60: Coef=–1.246; P=.04) compared to the control group. We were able to demonstrate a significant correlation between the HECSI calculated based on pictures uploaded by patients through the app and the HECSI assessed during personal visits (ρ=0.885; P<.001), despite the potentially lower image quality of the pictures uploaded through the app. Conclusions: This study provides further evidence that digital health apps can provide valuable support in improving patient clinical outcomes and management, especially as the app-based assessment of hand and feed images appears to be reliable. Trial Registration: Deutsches Register Klinischer Studien DRKS00020963; https://drks.de/search/de/trial/DRKS00020963
CRIS-Team Scopus Importer:2025-01-31
Keywords: clinical outcome; dermatology; disease management; eczema; educational; eHealth; hand and foot eczema; mental health; mHealth; mobile phone; motor skills; pain; quality of life; smartphone application; support; teledermatology; telemedicine

Injustice at work and leukocyte glucocorticoid sensitivity: Findings from a cross-sectional study - Herr, Raphael M.; Loerbroks, Adrian; Van Vianen, Annelies E. M.; Hoffmann, Kristina; Fischer, Joachim E.; Bosch, Jos A. (Psychosomatic Medicine, 2015)
Organizational justice refers to perceived fairness at the workplace. Low organizational justice has been identified as a major source of distress and a predictor of poor health. Impaired regulation of immunological and inflammatory pathways may, in part, underlie these health effects. The present study investigated the association of organizational justice with leukocyte glucocorticoid sensitivity in vivo. Methods Organizational justice was assessed among 541 male factory workers (mean [standard deviation] age = 46 [9] years) by questionnaire. Cortisol release was measured at three time points before blood collection and summed as the area under the curve. Blood was used to assess leukocyte (white blood cell [WBC] count) subsets (neutrophils [%WBC], lymphocytes [%WBC], and the neutrophil/lymphocyte ratio). Glucocorticoid sensitivity was operationalized as the correlation between cortisol release and these hematologic parameters. Associations were adjusted for demographics, work characteristics, and life-style variables. Results A dose-response relationship between organizational justice and glucocorticoid sensitivity was found. Cortisol and hematologic parameters showed the expected significant association among individuals reporting high (all β values ≥ 26 all p values ≤.001) or medium organizational justice (all β values ≥ .15 all p values ≤.050), but not among those reporting low organizational justice (all β values ≤.04; all p values >.10). These regression slopes differed significantly between organizational justice groups (p values for interaction <.050). Conclusions Low justice at work is associated with an impaired ability of endogenous cortisol to regulate leukocyte distribution in vivo. These findings identify a novel biological pathway by which organizational justice may affect health.
CRIS-Team Scopus Importer:2022-11-28
Keywords: glucocorticoid resistance; glucocorticoid sensitivity; inflammation; organizational justice; social interaction; Work stress

Investigating the associations of self-rated health: Heart rate variability is more strongly associated than inflammatory and other frequently used biomarkers in a cross sectional occupational sample - Jarczok, Marc N.; Kleber, Marcus E.; Koenig, Julian; Loerbroks, Adrian; Herr, Raphael M.; Hoffmann, Kristina; Fischer, Joachim E.; Benyamini, Yael; Thayer, Julian F. (PLoS ONE, 2015)
The present study aimed to investigate the possible mechanisms linking a single-item measure of global self-rated health (SRH) with morbidity by comparing the association strengths between SRH with markers of autonomic nervous system (ANS) function, inflammation, blood glucose and blood lipids. Cross-sectional comprehensive health-check data of 3947 working adults (age 42±11) was used to calculate logistic regressions, partial correlations and compare correlation strength using Olkins Z. Adjusted logistic regression models showed a negative association between SRH (higher values indicating worse health) and measures of heart rate variability (HRV). Glycemic markers were positively associated with poor SRH. No adjusted association was found with inflammatory markers, BP or lipids. In both unadjusted and adjusted linear models Pearson's correlation strength was significantly higher between SRH with HRV measures compared to SRH with other biomarkers. This is the first study investigating the association of ANS function and SRH. We showed that a global measure of SRH is associated with HRV, and that all measures of ANS function were significantly more strongly associated with SRH than any other biomarker. The current study supports the hypothesis that the extent of brain-body communication, as indexed by HRV, is associated with self-rated health.
CRIS-Team Scopus Importer:2022-11-28

Lack of supportive leadership behavior predicts suboptimal self-rated health independent of job strain after 10 years of follow-up: findings from the population-based MONICA/KORA study - Schmidt, Burkhard; Herr, Raphael M.; Jarczok, Marc N.; Baumert, Jens; Lukaschek, Karoline; Emeny, Rebecca T.; Ladwig, Karl-Heinz (International Archives of Occupational and Environmental Health, 2018)
Objectives: Emerging cross-sectional research has identified lack of supportive leadership behavior (SLB) as a risk factor for workforce health. However, prospective evidence is hitherto lacking. SLB denotes support in difficult situations, recognition and feedback on work tasks. This study aims to determine the effect of SLB on suboptimal self-rated health (SRH) after 10 years considering potential moderators such as ages, sex, occupation and job strain. Methods: The sample included 884 employed participants drawn from the population-based prospective MONICA/KORA Study. SLB, SRH, as well as job strain were assessed by questionnaire. Logistic regressions estimated odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for the effect of SLB at baseline on suboptimal SRH at follow-up. Analyses were adjusted for age, gender, lifestyle (alcohol, smoking, physical activity), socioeconomic status as well as for SRH and job strain at baseline. Results: Lack of SLB was associated with suboptimal SRH at baseline [OR 2.00, (95% CI 1.19–3.46)] and at follow-up [OR 2.33, (95% CI 1.40–3.89)]. Additional adjustment for job strain did not substantially alter this association [OR 2.06, (95% CI 1.20–3.52)]. However, interactions between SLB and job strain as well as gender became evident, indicating moderating influences on the association between SLB and SRH. Conclusion: Lack of supportive leadership was associated with suboptimal SRH at 10 years’ follow-up in men, even if SRH at baseline and other risk factors were taken into account. This effect is likely to be moderated by job strain.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Cohort study; Leadership; Self-rated health; Work stress; Workforce

Long-term effectiveness of a stress management intervention at work: A 9-year follow-up study based on a randomized wait-list controlled trial in male managers - Li, Jian; Riedel, Natalie; Barrech, Amira; Herr, Raphael M.; Aust, Birgit; Moertl, Kathrin; Siegrist, Johannes; Guendel, Harald; Angerer, Peter (BioMed Research International, 2017)
Objective. Short- andmedium-termeffectiveness (up to 3 years) of individual level stressmanagement interventions (SMI) at work were demonstrated, yet long-term effectiveness remains unexplored.We therefore aimed to address this research gap. Methods. 94 male middle managers participated in a randomized wait-list controlled trial between 2006 and 2008 and in a post-trial-followup survey in 2015. During the first two years, all received an 18-hour psychotherapeutic SMI intervention which was based on the Effort-Reward Imbalance (ERI) model: tackling stressor on mismatch between effort and reward and promoting recovery on overcommitment. Work stress (i.e., ERI indicators) was the primary outcome, and the secondary outcome was depressive symptoms. The long-term effectiveness of the SMI was examined by mixed modeling, using an external control group (n = 94). Results. Effort and reward were substantially improved with significant intervention ∗ time interaction effects (p < 0.001) compared to the external control group; effects on overcommitment and depressive symptoms were also significant (p < 0.05 and p < 0.01, resp.), though their trajectories in the intervention group were less sustainable. Conclusions. The effectiveness of this psychotherapeutic SMI at work based on the ERI model was observed over a 9-year period, particularly on the effort-reward ratio.
CRIS-Team Scopus Importer:2022-11-28

Long-term effectiveness of stress management at work: Effects of the changes in perceived stress reactivity on mental health and sleep problems seven years later - Herr, Raphael M.; Barrech, Amira; Riedel, Natalie; Guendel, Harald; Angerer, Peter; Li, Jian (International Journal of Environmental Research and Public Health, 2018)
The reduction of stress reactivity resulting from stress management interventions prevents disorders and improves mental health, however, its long-term sustainability has been little examined. The objective of this study was, therefore, to determine the effectiveness of a stress management intervention, designed to improve stress reactivity, for mental health and sleep problems seven years later, using longitudinal data from 101 male industrial workers. Linear regressions estimated the adjusted effects of the changes in stress reactivity in general as well as in its six subdimensions (work overload, social conflict, social stress, failure at work, and anticipatory and prolonged reactivity) on depression, anxiety, and sleep problems seven years later. The improvement of the prolonged reactivity had positive effects on depression, anxiety, and sleep problems (unstandardized regression coefficients [Bs] ≥ 0.35, all p-values ≤ 0.01). Depression and sleep problems were further improved by a reduction of the reactivity to social conflicts (Bs ≥ 0.29, p-values < 0.05), and an improvement in the overall reactivity score positively influenced sleep problems (B = 0.07, p = 0.017). In conclusion, the improvement of stress reactivity resulting from a work stress intervention was effective and generally long-lasting in preventing mental health and sleep problems. The reduction of the prolonged reactivity seems of particular importance and efficient in inhibiting negative stress manifestations.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Long-term effectiveness; Longitudinal; Mental health; Sleep problems; Stress management intervention; Stress reactivity; Work stress

Modifying health behavior to prevent cardiovascular diseases: A nationwide survey among German primary care physicians - Schneider, Sven; Diehl, Katharina; Bock, Christina; Herr, Raphael M.; Mayer, Manfred; Goerig, Tatiana (International Journal of Environmental Research and Public Health, 2014)
Cardiovascular diseases (CVD) are a major public health concern as they are the leading cause of death in developed countries. Primary care is considered to be the ideal setting for CVD prevention. Therefore, more than 4, 000 German primary care physicians (PCPs) were asked about their attitudes towards and their activities regarding the prevention of CVD in the nationwide ÄSP-kardio Study. The focus of the study was on health behavior modification. Two thirds of the participating PCPs stated that they routinely provided brief inventions to assist patients in reducing both their tobacco (72%) and alcohol (61%) consumption, to encourage them to increase their levels of physical activity (72%), and to assist them in adjusting to a more healthy diet (66%), and in achieving a healthy body weight (69%). However, only between 23% (quitting smoking) and 49% (diet modification) of PCPs felt that they had been successful in helping patients modify their lifestyles. Insufficient reimbursement, cultural diversity and a lack of time were reported to be the most problematic barriers to successful intervention in the primary care setting. Despite these obstacles, the majority of German PCPs was engaged in prevention and health behavior intervention to reduce the incidence and progression of CVD. © 2014 by the authors; licensee MDPI, Basel, Switzerland.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Cardiovascular diseases; Counseling; General practitioner; Health; Health behavior; Prevention; Preventive measures; Primary care physician

Nine-year longitudinal psychosocial and mental outcomes of a stress management intervention at work using psychotherapeutic principles - Li, Jian; Riedel, Natalie; Barrech, Amira; Herr, Raphael M.; Aust, Birgit; Moertl, Kathrin; Siegrist, Johannes; Guendel, Harald; Angerer, Peter (Psychotherapy and Psychosomatics, 2017)
CRIS-Team Scopus Importer:2022-11-28

Organizational Justice Is Related to Heart Rate Variability in White-Collar Workers, but Not in Blue-Collar Workers—Findings from a Cross-Sectional Study - Herr, Raphael M.; Bosch, Jos A.; Van Vianen, Annelies E. M.; Jarczok, Marc N.; Thayer, Julian F.; Li, Jian; Schmidt, Burkhard; Fischer, Joachim E.; Loerbroks, Adrian (Annals of Behavioral Medicine, 2015)
Background: Perceived injustice at work predicts coronary heart disease. Vagal dysregulation represents a potential psychobiological pathway.Purpose: We examined associations between organizational justice and heart rate variability (HRV) indicators. Grounded in social exchange and psychological contract theory, we tested predictions that these associations are more pronounced among white-collar than among blue-collar workers.Methods: Cross-sectional data from 222 blue-collar and 179 white-collar men were used. Interactional and procedural justice were measured by questionnaire. Ambulatory HRV was assessed across 24 h. Standardized regression coefficients (β) were calculated.Results: Among white-collar workers, interactional justice showed positive relationships with 24-h HRV, which were strongest during sleeping time (adjusted βs ≥0.26; p values ≤0.01). No associations were found for blue-collar workers. A comparable but attenuated pattern was observed for procedural justice.Conclusions: Both dimensions of organizational injustice were associated with lowered HRV among white-collar workers. The impact of justice and possibly its association with health seems to differ by occupational groups.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Blue-collar; Heart rate variability; Interactional justice; Occupational group; Organizational justice; Procedural justice; White-collar

Organizational justice, justice climate, and somatic complaints: A multilevel investigation - Herr, Raphael M.; Bosch, Jos A.; Loerbroks, Adrian; Genser, Bernd; Almer, Christian; Van Vianen, Annelies E. M.; Fischer, Joachim E. (Journal of Psychosomatic Research, 2018)
Objective: Organizational justice refers to perceived fairness at the workplace. Individual perceptions of injustice have been linked to reduced mental and physical health. However, perceptions of injustice also exist at the aggregate level of departments, reflecting a shared perception, denoted as justice climate. There is evidence that this shared perception independently predicts individual distress levels (e.g., anxiety, depression), which might negatively affect somatic symptom perception and reporting. Hence, the objective of this study was to examine whether individual perceptions of poor justice as well as a poor justice climate are related to elevated somatic complaints. In addition, this study examined if justice climate moderates the relationship between individual-level justice perceptions and somatic symptom reporting. Methods: Cross-sectional data from a large industrial manufacturing company was used, involving 1,102 employees in 31 departments. A validated scale covering interactional and procedural justice assessed individual-level organizational justice. A 19-item symptom checklist measured somatic complaints. Multilevel analyses estimated individual-level associations (within-department effects) with somatic complaints, department-level associations (between-department effects), and the cross-level interaction of both. Results: Individual-level justice perceptions were negatively associated with somatic complaints. Collective justice climate was likewise significantly associated with somatic complaints. There was no indication for a moderation effect of justice climate. Conclusion: A poor justice climate correlated positively with individual somatic complaints while controlling for individual perceptions, i.e., above and beyond individual justice perceptions. These findings may imply that interventions targeting department-level perceptions of justice may have the potential to reduce individual somatic complaints beyond the effects of individual-level interventions.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Justice climate; Multilevel; Organizational justice; Somatic complaints; Workplace

Patient preferences for biologicals in psoriasis: Top priority of safety for cardiovascular patients - Schaarschmidt, Marthe-Lisa; Kromer, Christian; Herr, Raphael M.; Schmieder, Astrid; Sonntag, Diana; Goerdt, Sergij; Peitsch, Wiebke K. (PLoS ONE, 2015)
Patients with psoriasis are often affected by comorbidities, which largely influence treatment decisions. Here we performed conjoint analysis to assess the impact of comorbidities on preferences of patients with moderate-to-severe psoriasis for outcome (probability of 50% and 90% improvement, time until response, sustainability of success, probability of mild and severe adverse events (AE), probability of ACR 20 response) and process attributes (treatment location, frequency, duration and delivery method) of biologicals. The influence of comorbidities on Relative Importance Scores (RIS) was determined with analysis of variance and multivariate regression. Among the 200 participants completing the study, 22.5% suffered from psoriatic arthritis, 31.5% from arterial hypertension, 15% from cardiovascular disease (myocardial infarction, stroke, coronary artery disease, and/or arterial occlusive disease), 14.5%from diabetes, 11% from hyperlipidemia, 26% from chronic bronchitis or asthma and 12.5% from depression. Participants with psoriatic arthritis attached greater importance to ACR 20 response (RIS = 10.3 vs. 5.0, p<0.001; ß = 0.278, p<0.001) and sustainability (RIS = 5.8 vs. 5.0, p = 0.032) but less value to time until response (RIS = 3.4 vs. 4.8, p = 0.045) than those without arthritis. Participants with arterial hypertension were particularly interested in a low risk of mild AE (RIS 9.7 vs. 12.1; p = 0.033) and a short treatment duration (RIS = 8.0 vs. 9.6, p = 0.002). Those with cardiovascular disease worried more about mild AE (RIS = 12.8 vs. 10, p = 0.027; ß = 0.170, p = 0.027) and severe AE (RIS = 23.2 vs. 16.2, p = 0.001; ß = 0.203, p = 0.007) but cared less about time until response (ß = -0.189, p = 0.013), treatment location (ß = -0.153, p = 0.049), frequency (ß = -0.20, p = 0.008) and delivery method (ß = -0.175, p = 0.023) than others. Patients' concerns should be addressed in-depth when prescribing biologicals to comorbid patients, keeping in mind that TNF antagonists may favourably influence cardiovascular risk.
CRIS-Team Scopus Importer:2022-11-28

Patient preferences for treatment of basal cell carcinoma: Importance of cure and cosmetic outcome - Martin, Isabelle; Schaarschmidt, Marthe-Lisa; Glocker, Anne; Herr, Raphael M.; Schmieder, Astrid; Goerdt, Sergij; Peitsch, Wiebke K. (Acta Dermato-Venereologica, 2016)
Treatment options for localized resectable basal cell carcinoma (BCC) include micrographically controlled surgery, simple excision, curettage, laser ablation, cryosurgery, imiquimod, 5-fluorouracil, photodynamic therapy and radiotherapy. The aim of this study was to assess the preferences of patients with BCC for outcome (cure and recurrence rate, cosmetic outcome, risk of temporary and permanent complications) and process attributes (type of therapy, treatment location, anaesthesia, method of wound closure, duration of wound healing, out-ofpocket costs) of these treatments with conjoint analysis. Participants (n = 124) attached greatest importance to recurrence rate (relative importance score (RIS) 17.28), followed by cosmetic outcome (RIS 16.90) and cure rate (RIS 15.02). Participants with BCC on the head or neck were particularly interested in cosmetic outcome. Those with a recurrence were willing to trade risk of recurrence, treatment location and duration of wound healing for a better cosmetic result. In summary, participants particularly valued cure and cosmetic outcome, although preferences varied with individual and tumour-associated characteristics.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Basal cell carcinoma; Conjoint analysis; Cosmetic outcome; Discrete choice; Excision; Patient preferences

Patient preferences for treatment of psoriasis with biologicals: A discrete choice experiment - Kromer, Christian; Schaarschmidt, Marthe-Lisa; Schmieder, Astrid; Herr, Raphael M.; Goerdt, Sergij; Peitsch, Wiebke K. (PLoS ONE, 2015)
Treatment dissatisfaction and non-adherence are common among patients with psoriasis, partly due to discordance between individual preferences and recommended treatments. However, patients are more satisfied with biologicals than with other treatments. The aim of our study was to assess patient preferences for treatment of psoriasis with biologicals by using computer-based conjoint analysis. Biologicals approved for psoriasis in Germany were decomposed into outcome (probability of 50% and 90% improvement, time until response, sustainability of success, probability of mild and severe adverse events (AE), probability of American College of Rheumatology (ACR) 20 response) and process attributes (treatment location, frequency, duration and delivery method). Impact of sociodemographic and socioeconomic characteristics and disease severity on Relative Importance Scores (RIS) of each attribute was assessed with analyses of variance, post hoc tests, and multivariate regression. Averaged across the cohort of 200 participants with moderate-to-severe psoriasis, preferences were highest for avoiding severe AE (RIS = 17.3), followed by 90% improvement (RIS = 14.0) and avoiding mild AE (RIS = 10.5). Process attributes reached intermediate RIS (8.2-8.8). Men were more concerned about efficacy than women (50% improvement: RIS = 6.9 vs. 9.5, p = 0.008; β = -0.191, p = 0.011 in multivariate models; 90% improvement: RIS = 12.1 vs. 15.4, p = 0.002; β = -0.197, p = 0.009). Older participants judged the probability of 50% and 90% improvement less relevant than younger ones (50% improvement: Pearson's Correlation (PC) = -0.161, p = 0.022; β = -0.219, p = 0.017; 90% improvement: PC = -0.155, p = 0.028; β = -0.264, p = 0.004) but worried more about severe AE (PC = 0.175, p = 0.013; β = 0.166, p = 0.082). In summary, participants with moderate-to-severe psoriasis were most interested in safety of biologicals, followed by efficacy, but preferences varied with sociodemographic characteristics and working status. Based on this knowledge, physicians should identify preferences of each individual patient during shared decision-making in order to optimize treatment satisfaction, adherence and outcome.
CRIS-Team Scopus Importer:2022-11-28

Patients' and Physicians' Preferences for Systemic Psoriasis Treatments: A Nationwide Comparative Discrete Choice Experiment (PsoCompare) - Schaarschmidt, Marthe-Lisa; Herr, Raphael M.; Gutknecht, Mandy; Wroblewska, Katharina; Gerdes, Sascha; Sticherling, Michael; Augustin, Matthias; Peitsch, Wiebke K. (Acta Dermato-Venereologica, 2018)
Systemic antipsoriatic treatment options are increasing rapidly. The aim of this nationwide discrete choice experiment was to compare patients' (n = 222) and physicians' (n = 78) preferences for outcome and process attributes of systemic antipsoriatics using Relative Importance Scores (RIS). Both groups considered Psoriasis Area and Severity Index 90 (PASI 90) to be most important (RIS 21.4 and 20.8, respectively). Moreover, patients were highly concerned about mild and severe adverse events (RIS = 18.2 and 14.2), physicians about severe adverse events (RIS = 14.9) and cost (RIS = 13.8). Compared to physicians, patients worried more about mild adverse events and treatment location, but less about cost and frequency of laboratory tests. Physicians' preferences were influenced by work experience and percentage of biological prescriptions, patients' preferences by age, disease duration and severity. Older and less severely affected patients recruited via a patient organization focused more on safety, but less on efficacy and time until response than did patients from study centres. In conclusion, these differences in trade-offs should be integrated into a shared decision-making.
EVALuna2:34404

Perceived importance of pandemic interventions for attending cultural events – findings from Germany - Weber, Michaela; Plew, Manuel; Neumann, Christine; Ostendorf, Marietta; Herr, Raphael M.; Fischer, Joachim (BMC Public Health, 2022)
Background: During the first waves of the COVID-19 pandemic, many cultural and sporting events were held without spectators or had to be cancelled. Therefore, several containment strategies to provide requirements for safe events were developed and tested. Nonetheless, every second (50.7%) is afraid of becoming infected on an event. We therefore investigated which hygiene and containment measures are perceived to be important from the visitor’s point of view and thus might increase subjective sense of safety. Methods: This online study was carried out in November 2020. A total of 1,004 persons, who regularly attended events before the pandemic, took part in the study. The importance of different hygiene and containment measures was evaluated using a 5-point Likert-scale (1 “unimportant” to 5 “extremely important”). Potential statistical differences in socio-demographical aspects (age, gender, net disposable income for leisure activities) and attendance on events were tested with analyses of variance. Results: Participants perceived the use of disinfectant (M = 4.10) as the most important element of containment strategies, followed by transparent information on the hygiene strategy (M = 4.00), reduced occupancy (M = 3.98), and optimized ventilation (M = 3.97). Body temperature measurement at the entrance (M = 3.27), a negative SARS-CoV-2 test (M = 3.11), completion of a health questionnaire (M = 3.05), and abandoning breaks and catering (M = 2.98) were considered as less important. Analyses of group differences in socio-demographical aspects found abandoning breaks and catering to be more important to men than to women. This strategy is also more important to people aged 66 and above than to younger age groups (e.g., age 20–40). For women, the use of disinfectant is considerably more important. No other significant differences exist. Conclusion: Combining relevant measures appears to be important to provide a safe containment strategy. Measures aimed at positively influencing people’s sense of safety do not fully correspond to researched knowledge of effectiveness. There are also target group-specific differences in the rating of measures, which should be considered while preparing containment strategies. To describe the dynamic development of changes in subjective rating of containment strategies, continuing research is needed.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Containment; Coronavirus; COVID-19; Events; Pandemic; Relevance; Reopening; Safety

Perceived Unfairness in University Settings: Findings from a Qualitative Study among Students in Germany - Herr, Raphael; Deyerl, Veronika; Rathmann, Katharina; Diehl, Katharina (Education Sciences, 2024)
In universities, perceived unfairness is associated with negative outcomes, such as dissatisfaction, lower engagement, higher drop-out and stress, and poorer mental health. It is, however, still unclear which aspects constitute perceived unfairness in students. Therefore, this qualitative study explored students’ perceptions of unfairness with twenty semi-structured interviews. The interviews were audiotaped, transcribed verbatim, and analyzed following Mayring’s qualitative content analysis. A set of main codes and subcodes was developed and refined. The identified sources of unfairness can be summarized as organizational aspects, such as the registration and administration processes, the treatment of students, including the behavioural patterns of lecturers and university staff, and the individual situation of students. This study identified different sources of perceived unfairness in the university setting, potentially related to less engagement, higher drop-out rates, and worse mental health of the students. To keep students engaged and healthy, it seems beneficial to address the sources of unfairness.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Germany; injustice; mental health; qualitative; stress; students; unfairness; university setting

Perceived university unfairness and somatic symptoms in German students: mediation by distress and lifestyle - Herr, Raphael; Deyerl, Veronika; Södel, Corinna; Diehl, Katharina (International Journal of Adolescence and Youth, 2025)
Perceived unfairness at the university is a stressor for students and may be a risk factor for somatic symptoms. Therefore, this study examined the association of perceived unfairness with somatic symptoms and the mediating role of distress and lifestyle factors in 1,105 university students from Germany (50.1% female, mean age: 25.51). The participants filled out an online questionnaire in March 2024 capturing somatic symptoms (SSS-8), perceived university unfairness (UFair Questionnaire), alcohol consumption (AUDIT-C), physical activity, sleep quality (Jenkins Sleep Scale), and distress (SOS-XS-G). Multiple mediation of the association of perceived unfairness with self-reported somatic symptoms by distress and/or lifestyle factors was analysed. The model was adjusted for age, gender, and university type. The association between perceived university unfairness and somatic symptoms was notable (direct standardized effect: 0.524, p < 0.001) and partially mediated by distress, and sleep quality. Consequently, the reduction of perceived university unfairness might reduce their distress, improve their sleep quality, and reduce their somatic symptoms.
CRIS-Team Scopus Importer:2025-04-18
Keywords: distress; injustice; somatic symptoms; students; Unfairness; university

Personality and risk of adult asthma in a prospective cohort study - Loerbroks, Adrian; Li, Jian; Bosch, Jos A.; Herr, Raphael M.; Angerer, Peter (Journal of Psychosomatic Research, 2015)
Objective: Traits conceptualized according to the five-factor model of personality have been found to predict numerous health outcomes and may also be predictive of asthma. Prior longitudinal studies on personality and asthma remain however sparse, have been restricted to only two traits (i.e., neuroticism and extraversion), and yielded inconsistent results. We therefore aimed to examine the potential relationships of all five-factor personality traits with incident asthma. Methods: We combined the 2009 and 2011 data from the population-based German Socio-Economic Panel study for longitudinal analyses (n = 12,202). Personality traits were measured by an established 15-item version of the Big Five Inventory. Asthma was measured by participant-reports of having ever received such a diagnosis by a physician. We estimated multivariable risk ratios (RRs) and corresponding 95% confidence intervals (CIs) of trait-specific scores (continuous or categorized by tertiles) and incident asthma by Poisson regression. Results: Neuroticism was the only trait which was predictive of asthma (RR for the z-score = 1.17, 95% CI = 1.02-1.34; RR for the highest versus the lowest tertile = 1.59, 95% CI = 1.12-2.25). Associations between personality traits and asthma risk did not differ by sex (p-values for interaction ≥. 0.07). There were no two-way interactions between personality traits when we tested all potential combinations (all p-values for interaction ≥. 0.20). Conclusion: The present study suggests that high levels of neuroticism may predispose adults to develop asthma. Future longitudinal studies are needed to confirm our findings and to shed light on the potential psychophysiological processes underlying the observed association.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Asthma; Epidemiology; Germany; Personality

Personality type matters: Perceptions of job demands, job resources, and their associations with work engagement and mental health - Herr, Raphael M.; Van Vianen, Annelies E. M.; Bosle, Catherin; Fischer, Joachim E. (Current Psychology, 2021)
This three-wave study examined whether the pattern of associations of job demands and job resources with work engagement and mental health depends on personality types. In a representative sample of the German workforce (N = 13,665), the Big Five personality traits could be used to cluster participants into five personality types: ordinary, resilient, strained, overcontrolled, and undercontrolled. As predicted, job demands were associated with mental health and job resources were primarily associated with work engagement. However, these relationships differed across personality types. We conclude that research and practice could take a more personality-driven stance towards employee perceptions of job demands and job resources and their associations with work engagement and mental health.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Job demands; Job resources; Mental health; Personality types; Work engagement

Pharyngeal chemosensitivity in patients with obstructive sleep apnea and healthy subjects - Heiser, Clemens; Zimmermann, Ingo; Sommer, J. Ulrich; Hoermann, Karl; Herr, Raphael M.; Stuck, Boris A. (Chemical Senses, 2013)
Signs of pharyngeal neurodegeneration have been detected in patients with obstructive sleep apnea (OSA). Along with this neurodegeneration, a decreased pharyngeal sensitivity to mechanical stimulation has been described. The decreased sensitivity may play a role in the pathophysiology of this disease. The aim of the study was to investigate the chemosensitivity of the pharyngeal mucosa in patients with OSA compared with controls. Healthy controls and patients with OSA (age: 30-60 years) were included. Testing of oropharyngeal chemosensitivity was performed with subjective intensity ratings of capsaicin (SIR, visual analogue scale 0-10), air puffs (presented with an olfactometer), and stimulation with CO2 at the posterior pharyngeal wall. A 2-point discrimination test at the soft palate, an intensity rating of capsaicin at the tongue, and a nasal lateralization test were performed. Twenty-six patients with OSA and 18 healthy controls were included. No differences were detected in the SIR of capsaicin at the tongue or in the nasal lateralization test. At the pharynx, a decreased sensitivity to capsaicin (OSA: 6.8 ± 2.3; healthy control: 8.6 ± 1.3), air puffs (OSA: 2.8 ± 1.9; healthy control: 4.2 ± 1.6), and stimulation with CO2 (OSA: 1.5 ± 1.7; healthy control: 2.8 ± 1.8) were demonstrated in patients with OSA (all P < 0.05). Two-point discrimination at the soft palate was reduced with statistical significance in the OSA group (OSA: 11.5 ± 5.4 mm; healthy control: 5.0 ± 2.4 mm). The results suggest reduced pharyngeal chemosensitivity in OSA patients in addition to the reduced mechanical pharyngeal sensitivity shown with 2-point discrimination. This demonstrates peripheral neurodegeneration in the context of this disease. © The Author 2013. Published by Oxford University Press. All rights reserved.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Neurodegeneration; Obstructive sleep apnea; Pharyngeal chemosensitivity; Trigeminal; Vibration damage soft palate

Physical activity counseling by primary care physicians: Attitudes, knowledge, implementation, and perceived success - Diehl, Katharina; Mayer, Manfred; Mayer, Frank; Goerig, Tatiana; Bock, Christina; Herr, Raphael M.; Schneider, Sven (Journal of physical activity and health, 2015)
Background: In physical activity (PA) counseling, primary care physicians (PCPs) play a key role because they are in regular contact with large sections of the population and are important contact people in all health-related issues. However, little is known about their attitudes, knowledge, and perceived success, as well as about factors associated with the implementation of PA counseling. Methods: We collected data from 4074 PCPs including information on physician and practice characteristics, attitudes toward cardiovascular disease (CVD) prevention, and measures used during routine practice to prevent CVD. Here, we followed widely the established 5 A's strategy (Assess, Advise, Agree, Assist, Arrange). Results: The majority (87.2%) of PCPs rated their own level of competence in PA counseling as 'high,' while 52.3% rated their own capability to motivate patients to increase PA as 'not good.' Nine of ten PCPs routinely provided at least 1 measure of the modified 5 A's strategy, while 9.5% routinely used all 5 intervention strategies. Conclusions: The positive attitude toward PA counseling among PCPs should be supported by other stakeholders in the field of prevention and health promotion. An example would be the reimbursement of health counseling services by compulsory health insurance, which would enable PCPs to invest more time in individualized health promotion.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Cardiovascular diseases; General practitioners; Prevention

Physician Gender and Lifestyle Counselling to Prevent Cardiovascular Disease: A Nationwide Representative Study - Diehl, Katharina; Gansefort, Dirk; Herr, Raphael M.; Görig, Tatiana; Bock, Christina; Mayer, Manfred; Schneider, Sven (Journal of Public Health Research, 2015)

Primary school teachers in China: associations of organizational justice and effort–reward imbalance with burnout and intentions to leave the profession in a cross-sectional sample - Loerbroks, Adrian; Meng, Heng; Chen, Min-Li; Herr, Raphael M.; Angerer, Peter; Li, Jian (International Archives of Occupational and Environmental Health, 2014)
Objective: We examined associations of organizational justice (OJ) and effort–reward imbalance (ERI) with burnout and intentions to leave the teaching profession (ILTP) among primary school teachers in China.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Effort–reward imbalance; Organizational justice; People’s Republic of China; Professional burnout; Teachers; Turnover intention

Psychische Gesundheit bei der Arbeit – Der psy50 als integrativer Ansatz zur Messung der Arbeitsbedingungen - Fischer, Joachim E.; Brokmeier, Luisa; Herr, Raphael M.; et al. (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2022)
Work can either stabilize or impair mental health. Thus, factors that support well-being and commitment must be considered in addition to burdens and stressors. Further, without knowledge of the mental well-being or engagement of the workers, the assessment of psychosocial working conditions remains incomplete. Long-term studies show that the lack of or variation in resources correlates more strongly with engagement, emotional well-being or health-related productivity losses than stressors. The effects differ across personality types. Methodological advances allow the development of compact screening instruments which cover all relevant constructs yet can be completed in less than 10 minutes. The second part of the article presents such an instrument, the psy50. The instrument was developed over several years in cooperation with the BKK umbrella organization, the Federal Ministry of Labour, experts and employees as part of the psyGA project.<br

Psychometric properties of a German organizational justice questionnaire (G-OJQ) and its association with self-rated health: Findings from the Mannheim Industrial Cohort Studies (MICS) - Herr, Raphael M.; Li, Jian; Bosch, Jos A.; Schmidt, Burkhard; Dejoy, David M.; Fischer, Joachim E.; Loerbroks, Adrian (International Archives of Occupational and Environmental Health, 2014)
Purpose: The objective of the present study was to validate a German 11-item organizational justice questionnaire (G-OJQ) that consists of two subscales, referred to as "procedural justice" (PJ) and "interactional justice" (IJ) adapted from Moorman's organizational justice (OJ) questionnaire. A second objective was to determine associations of the G-OJQ with self-rated health. Methods: This study used cross-sectional data from an occupational cohort of 1518 factory workers from Germany (87.7 % male; mean age = 38.8 with SD = 11.9). After splitting the sample in two random subsamples, we assessed structural validity by exploratory factor analyses in one subsample and by confirmatory factor analysis in the other subsample. Internal validity was assessed by Cronbach's α. Associations with self-reported poor health were estimated by logistic regression. Results: The full scale and its subscales yielded Cronbach's α's of ≥0.9, and item-total correlations were ≥0.5. Factor analyses confirmed the expected 2-factor structure, labeled "interactional justice" (IJ, 4 items, λ 0.43-0.94) and "procedural justice" (PJ, 7 items, λ 0.46-0.83), respectively, and showed an acceptable fit to the data (χ 2 = 61; p =.001; CFI = 0.995; RMSEA = 0.037). The OJ total score as well as subscale scores in the lowest quartile, when compared to the highest quartile, was associated with an ≥2.3 increased odds of reporting poor health. Conclusion: The G-OJQ seems to be a valid and useful tool for observational and intervention studies in occupational settings. Future studies may additionally explore longitudinal associations and test the generalizability of the present findings to other populations and health outcomes. © 2012 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Epidemiology; Germany; Occupational health; Organizational justice

Psychosocial resources and the relationship between transformational leadership and employees' psychological strain - Schmidt, Burkhard; Loerbroks, Adrian; Herr, Raphael M.; Litaker, David; Wilson, Mark; Kastner, Michael; Fischer, Joachim (Work : a journal of prevention, assessment & rehabilitation, 2014)
Background: Leadership behavior may both serve as a supportive resource or as a source of psychological distress in the workplace.
CRIS-Team Scopus Importer:2022-11-28
Keywords: leadership; mediation; Stress; workplace

Reply to "job stress and metabolic syndrome with special reference to sex and age" by T. Kawada - Schmidt, Burkhard; Herr, Raphael M.; Bosch, Jos A. (International Journal of Cardiology, 2015)
CRIS-Team Scopus Importer:2022-11-28
Keywords: Age; Effort-reward imbalance; Job stress; Metabolic syndrome; Sex; Workplace

Reports of wheezing and of diagnosed asthma are associated with impaired social functioning: Secondary analysis of the cross-sectional World Health Survey data - Loerbroks, Adrian; Bosch, Jos A.; Sheikh, Aziz; Yamamoto, Shelby; Herr, Raphael M. (Journal of Psychosomatic Research, 2018)
Objective We sought to investigate whether there are associations between asthma and social functioning in adults from Western and non-Western countries. Methods We analyzed data on individuals (94% aged 20 +, 52% female) from 50 countries participating in the cross-sectional World Health Survey. We used information on self-reports of wheezing and an asthma diagnosis. Social functioning was defined by reports of severe or extreme difficulties related to personal relationships or participation in the community. Logistic regression was used to estimate adjusted odds ratios (ORs) and 95% confidence intervals (CIs). Results Wheezing was associated with impaired social functioning both in the overall sample (OR = 2.40, 95%CI = 2.09–2.75) and in Africa, South America and Asia (ORs ≥ 2.47), but not in Europe (aOR = 1.26, 95%CI = 0.90–1.77). Analyses with self-reports of diagnosed asthma yielded similar, albeit weaker, associations (e.g. OR for the overall sample = 1.63, 95%CI = 1.38–1.92). We also combined asthma and wheezing into a single variable (reference group: no asthma diagnosis/no wheezing). We observed that in particular reports of wheezing were associated with impaired social functioning regardless of whether a concomitant asthma diagnosis was reported (OR = 2.19, 95%CI = 1.81–2.64) or not (OR = 2.50, 95%CI = 2.09–2.99). Conclusion Self-reports of wheezing and of diagnosed asthma are associated with impaired social functioning among adults in Africa, South America and Asia, but less so in Europe. These relationships are mainly driven by the experience of respiratory symptoms (i.e. wheezing). Our findings may partly be explained by regional variations in asthma control. Further research should elucidate the determinants and mechanisms of asthma-related impaired social functioning.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Asthma; Epidemiology; Social functioning; Social participation; Wheezing; World Health Organization

Role of contextual and compositional characteristics of schools for health inequalities in childhood and adolescence: A scoping review - Herke, Max; Moor, Irene; Winter, Kristina; Hack, Miriam; Hoffmann, Stephanie; Spallek, Jacob; Hilger-Kolb, Jennifer; Herr, Raphael M.; Pischke, Claudia; Dragano, Nico; Novelli, Anna; Richter, Matthias (BMJ Open, 2022)
Objectives To synthesise the evidence on the role of compositional or contextual characteristics of schools in the association between students' socioeconomic position and their health in primary and secondary education in developed economies. Design Scoping review. We included studies examining the role of at least one school or class characteristic on students' health inequalities and was published since 1 January 2000, in English or German. We searched PubMed/Medline, Web of Science and Education Resources Information Center. We provided a narrative synthesis and an overview of findings. School characteristics were grouped into five broad categories: school composition, school climate, school policies and organisation, food environment and facilities. Results Of 8520 records identified, 26 studies were included. Twelve studies found a moderating and 3 a mediating effect. The strongest evidence came from studies examining the moderating effect of school composition, that is, the negative impact of a low individual socioeconomic position on mental health and well-being was aggravated by a low average socioeconomic position of schools. Evidence concerning the role of school climate, school stratification (eg, performance base tracking) and sponsorship, food environment and sport facilities and equipment was generally weak or very weak and mostly based on singular findings. Overall, favourable meso-level characteristics mitigated the negative impact of low individual socioeconomic position on health outcomes. Conclusions School characteristics affect health inequalities in children and adolescents to some degree, but future research is necessary to strengthen the existing evidence and address under-represented aspects in school characteristics and health outcomes.
CRIS-Team Scopus Importer:2022-11-28
Keywords: community child health; health policy; public health

Social Connections in the Workplace - Birmingham, Wendy C.; Holt-Lunstad, Julianne; Herr, Raphael; Barth, Abigail (American Journal of Health Promotion, 2024)
CRIS-Team Scopus Importer:2024-08-16

Socioeconomic position and self-rated health among female and male adolescents: The role of familial determinants in explaining health inequalities. Results of the German KiGGS study - Rattay, Petra; Blume, Miriam; Wachtler, Benjamin; Wollgast, Lina; Spallek, Jacob; Hoffmann, Stephanie; Sander, Lydia; Herr, Raphael M.; Herke, Max; Reuter, Marvin; Novelli, Anna; Hoevener, Claudia (PLoS ONE, 2022)
Objective Although health inequalities in adolescence are well documented, the underlying mechanisms remain unclear. Few studies have examined the role of the family in explaining the association between the family’s socioeconomic position and adolescents’ self-rated health. The current study aimed to explore whether the association between socioeconomic position and self-rated health was mediated by familial determinants. Methods Using data from wave 2 of the”German Health Interview and Examination Survey for Children and Adolescents” (KiGGS) (1,838 female and 1,718 male 11- to 17-year-olds), linear regression analyses were conducted to decompose the total effects of income, education, occupational status, socioeconomic position index and adolescents’ subjective social status on self-rated health into direct effects and indirect effects through familial determinants (family cohesion, parental well-being, parental stress, parenting styles, parental obesity, smoking and sporting activity). Results A significant total effect of all socioeconomic position indicators on self-rated health was found, except for income in male adolescents. In female adolescents, more than 70% of the total effects of each socioeconomic position indicator were explained by familial mediators, whereas no significant direct effects remained. The most important mediator was parental well-being, followed by family cohesion, parental smoking and sporting activity. In male adolescents, the associations between income, parental education, the socioeconomic position index and subjective social status were also mediated by familial determinants (family cohesion, parental smoking, obesity and living in a single-mother family). However, a significant direct effect of subjective social status remained. Conclusion The analysis revealed how a family’s position of socioeconomic disadvantage can lead to poorer health in adolescents through different family practices. The family appears to play an important role in explaining health inequalities, particularly in female adolescents. Reducing health inequalities in adolescence requires policy interventions (macro-level), community-based strategies (meso-level) and programs to improve parenting and family functioning (micro-level).
CRIS-Team Scopus Importer:2022-11-28

Sozialbedingte Ungleichheiten von Gesundheit und Gesundheitsverhalten bei Studierenden - Diehl, Katharina; Hilger-Kolb, Jennifer; Herr, Raphael M. (Gesundheitswesen, 2021)
Aim of the study Disease prevention and health science research have focused increasingly on students in recent years. However, students are usually perceived as a homogeneous group. The aim of this article was to examine if there exist health inequalities among students. Methods A nationwide student survey, the so-called NuPhA study, was used to answer this question (n=689, 69.5% female, average age: 22.69 years). Results and conclusions We found that socio-economic indicators were associated with health and health behavior. For instance, being a scholarship holder was associated with a better general, mental, and physical health. In particular, subjective social status was positively associated with better general, mental, and physical health as well as higher physical activity. The results indicate that while students initially appeared to form a homogenous group, health inequalities exist among them. This suggests the need for a differentiated view on the student group and the importance of examining and explaining health inequalities among students in depth and to finally reduce them.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Health; Health inequalities; Students; University

Stress at work is associated with intima media thickness in older male employees, independent of other sources of stress perception - Mauss, Daniel; Volmer-Thole, Maren; Herr, Raphael M.; Bosch, Jos A.; Fischer, Joachim E. (Stress. The International Journal on the Biology of Stress, 2021)
Chronic stress at work shows a moderate but robust longitudinal association with cardiovascular disease (CVD). Atherosclerosis is a pathophysiological process of most CVD, for which intima media thickness (IMT) of the carotid artery is used as an early marker. Its relationship with stress at work has remained largely unexplored, and the present study therefore aimed to elucidate the association between stress at work, assessed as effort-reward imbalance (ERI), and IMT. This cross-sectional study comprised of 501 male German employees aged 42 (19–64) years at enrollment into the Mannheim Industrial Cohort Study. Clinical assessments used fasting blood samples and IMT measurement. Self-report questionnaires assessed sources of perceived stress. Analyses adjusted for medical history, life style, and socio-economic status (SES) indicators as well as general perceived stress and worries to determine the specificity of ERI. Linear regression models estimated the association of ERI with IMT, stratifying for age groups and adjusting for potential confounders. ERI ratio increased until the age of 50 years and abated thereafter. In participants younger than 50 years IMT measurements were not associated with ERI ratios. However, despite lower mean ERI ratios in participants older than 50 years, this age group showed a significant relationship with IMT (standardized Beta =.36, p <.01), adjusting for multiple confounders including general perceived stress and worries. These analyses suggest that atherosclerosis in older employees is specifically related to stress at work. Longitudinal studies will help to elucidate the temporal relationship between stress exposure and downstream biological mechanisms.Lay summary Our study explored the association of job stress and the calcification of the carotid artery in German employees. We found out that this association is stronger in employees older than 50 years. In addition, it is independent of medical risk factors and stress caused by private issues.
CRIS-Team Scopus Importer:2022-11-28
Keywords: cardiovascular disease; effort-reward imbalance; ERI; IMT; PSS; Work stress

Terra incognita Hausarztpraxis – Tabakentwöhnung in der deutschen Primärversorgung - Schneider, Sven; Diehl, Katharina; Bock, Christina; Herr, Raphael M.; Mayer, Manfred; Lindinger, Peter; Görig, Tatiana (Sucht, 2014)
Objective: The family practice is said to be the ideal setting to initiate smoking cessation. The German nationwide study "ASP-kardio" delivers current data concerning the status quo of smoking cessation support offered in German family practices according to the "5 A's strategy". Methods: 4000 general practitioners were questioned in a representative survey between October 2011 and March 2012. Before that, the questionnaire had been revised by experts, validated by cognitive interviews and tested in a pilot study. Results: 89% of the general practitioners assessed tobacco consumption among their patients ("Assess"), 82% advised smokers to stop smoking ("Advise") and 12% fixed a written agreement on smoking cessation objectives as a matter of routine. Assistance ("Assist") in the form of a brief intervention was much more commonly offered (72%) than in the form of providing information leaflets (33%) or offering a smoking cessation therapy (27%). About half of the questioned general practitioners (54%) arranged a follow-up appointment to check if patients succeeded in quitting smoking ("Arrange"). The support offered depended on the general practitioner himself/herself, on the condition and location of the practice as well as on patient specific factors. In the federal states (Bundesländer) located in the northeast of Germany, the support offered was below average. Eight out of ten general practitioners (77%) said that their methods were not successful. Conclusion: The suboptimal and unequally distributed care of smokers offering appropriate smoking cessation measures in Germany's primary care becomes evident. © 2014 Verlag Hans Huber, Hogrefe AG.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Brief intervention; Counseling; General practitioners; Smoking; Smoking cessation

The association between diabetes and an episode of depressive symptoms in the 2002 World Health Survey: An analysis of 231 797 individuals from 47 countries - Mommersteeg, P. M. C.; Herr, Raphael M.; Pouwer, Frans; Holt, R. I. G.; Loerbroks, A. (Diabetic Medicine, 2013)
Aims: Depression is common in people with diabetes and increases the risk of poor health outcomes, including premature mortality. We explored the association between diabetes and an episode of depressive symptoms in a cross-sectional multinational study, which included a large number of low- and middle-income non-Western countries. Methods: Data from 47 countries of the 2002 World Health Organization World Health Survey were used, including 231 797 adults (mean age 41 years, 53% female). Diabetes was assessed by self-report of diagnosis or treatment. The presence of an episode of depressive symptoms was assessed by self-report using an algorithm based on DSM-IV criteria. Odds ratios and 95% confidence intervals were calculated to quantify associations between diabetes and episodes of depressive symptoms in the entire sample and for countries aggregated into four continents: Africa, South America, Asia and Europe. Odds ratios were adjusted for age, sex, education, BMI, smoking and physical activity level. Results: The prevalence of diabetes (mean 3.6%, range 0.2-13%) and episodes of depressive symptoms (mean 7.9%, range 0.4-38%) differed widely across countries. Globally, individuals with diabetes had increased odds of an episode of depressive symptoms compared with those without diabetes (adjusted odds ratio 2.36, 95% confidence interval 1.91-2.92). Similar associations were found in South America, Asia and Europe (odds ratio > 1.97), but not in Africa (odds ratio 0.86, 95% confidence interval 0.54-1.37). Conclusions: Globally, diabetes is associated with a twofold increased prevalence of an episode of depressive symptoms, except in Africa. Given the worldwide rise in diabetes in the coming decades, and the increased risk of poor diabetes outcomes associated with co-morbid depression, studies examining mechanisms and interventions are necessary. © 2013 Diabetes UK.
CRIS-Team Scopus Importer:2022-11-28

The association between supportive social ties and autonomic nervous system function—differences between family ties and friendship ties in a cohort of older adults - Bosle, Catherin; Brenner, Hermann; Fischer, Joachim E.; Jarczok, Marc N.; Schottker, Ben; Perna, Laura; Hoffmann, Kristina; Herr, Raphael M. (European Journal of Ageing, 2022)
Supportive family and friendship ties can serve different functions and thus might show different associations with an individual’s health. Particularly, older adults might show varying health benefits of different types of supportive ties depending on their marital and retirement status. Our aim is to analyze relationships between different types of supportive social ties and autonomic nervous system (ANS) function, a physiological indicator of health that can help to establish the biological plausibility of the association—measured by heart rate variability (HRV). We present cross-sectional linear regression analyses of a German cohort of community-dwelling older adults (2008–2010; n = 1,548; mean age = 68.7 years). Our findings indicate that supportive friendship ties show significant positive associations (i.e., higher HRV) in individuals that are either not married or above retirement age. Supportive family ties show significant positive associations in individuals below retirement age. Significant results vanish or are reduced after accounting for behavioral/physical and psychological/cognitive indicators. We conclude that programs supporting the development or maintenance of friendship ties might be especially beneficial in unmarried older adults and adults above retirement age.
CRIS-Team Scopus Importer:2022-11-28
Keywords: ANS function; Family ties; Friendship ties; Heart rate variability; Older adults; Social ties

The association of asthma and wheezing with major depressive episodes: An analysis of 245 727 women and men from 57 countries - Loerbroks, Adrian; Herr, Raphael M.; Subramanian, S. V.; Bosch, Jos A. (International Journal of Epidemiology, 2012)
Background: Epidemiological studies have shown that asthma is positively associated with depression. Most of this evidence stems from individual studies conducted in Western populations (e.g. Europe, North America and Australia). It is still unclear whether such findings generalize to non-Western countries. To address this question, the present study investigated the association of asthma and wheezing with depression in a large multi-national sample. Methods: We used data from the 2002 World Health Survey. Participants reported physician-diagnosed asthma and attacks of wheezing within the past 12 months. Questions on depressive symptoms, their duration and persistence were used to define presence of a major depressive episode (MDE) within the past 12 months. ORs and 95% CIs were estimated by logistic regression for the entire sample, by continent (Australia, Europe, South America, Asia and Africa) and by country. Complete information was available for 57 countries. Results: Both asthma and wheezing were associated with MDE in the entire sample (OR = 2.37, 95% CI = 2.10-2.66 and OR = 3.06, 95% CI = 2.75-3.40, respectively). Similar associations were found for all continents with generally stronger ORs in South America, Asia and Africa for both asthma (ORs ≥ 1.8) and wheezing (ORs ≥ 2.8). On the country level, wheezing showed a consistent pattern of association with MDE. Similar patterns were found for asthma. Conclusions: Despite a range of country differences that could affect the association of asthma with depression, such as access to health care, the results of this study indicate that the co-occurrence of asthma and depression is a universal phenomenon. © The Author 2012; all rights reserved.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Asthma; Depression; Epidemiology; WHO

The association of cortisol levels with leukocyte distribution is disrupted in the metabolic syndrome - Mauss, Daniel; Herr, Raphael M.; Jarczok, Marc N.; Motoc, Irina; Fischer, Joachim E.; Bosch, A. (OBES RES CLIN PRACT, 2021)
Background: Leukocyte glucocorticoid sensitivity (GCS) pertains to the responsivity of leukocytes to the regulating actions of glucocorticoids, such as cortisol. Impaired endocrine regulation may link the metabolic syndrome (MetS) to the development of cardiovascular disease. We tested if the physiological association between endogenous cortisol levels and peripheral leukocyte composition becomes disrupted in individuals with MetS. Methods: MetS was assessed among 689 German industrial employees. The covariance between cortisol levels and hematologic parameters (i.e., proportions of neutrophils and lymphocytes) and their ratio was explored, which has been proposed as a proxy for GCS in vivo. Cortisol level before blood collection was assessed by repeated saliva collection, and the area under the curve was calculated. Linear regression models were adjusted for potential confounders including age, gender, BMI, income, and lifestyle factors. Results: Cortisol levels did not differ between subgroups. Participants without MetS (n = 552) showed the expected association of cortisol with hematologic parameters (β = 0.207 to 0.216; p values < 0.001). No association (β = 0.078 to 0.083; p values > 0.10) was found among those with MetS (n = 137), consistent with a reduced GCS. Analyses of separate MetS components showed that reduced GCS was associated specifically with decreased high-density lipoprotein and elevated fasting plasma glucose. Conclusions: Utilizing a novel statistical approach to infer GCS, this study provided first epidemiological evidence of aberrant physiological regulation of leukocyte distribution by endogenous cortisol levels among individuals with MetS. These findings underline the idea that MetS may involve disruption of endocrine-immune regulation.
CRIS-Team Scopus Importer:2022-11-28
Keywords: cortisol; glucocorticoid resistance; glucocorticoid sensitivity; inflammation; metabolic syndrome

The association of depression and angina pectoris across 47 countries: Findings from the 2002 World Health Survey - Loerbroks, Adrian; Bosch, Jos Antonio; Mommersteeg, Paula Maria Christina; Herr, Raphael M.; Angerer, Peter; Li, Jian (European Journal of Epidemiology, 2014)
Comorbid depression predicts poor health outcomes in patients with angina pectoris (AP). However, epidemiological data on the depression-AP comorbidity is limited and largely restricted to studies from Western countries, making generalizability to other regions uncertain. We aimed to provide additional epidemiological data for non-Western as well as Western countries. The present study used population-based data gathered in 47 countries from four continents (Africa, Asia, South America, and Europe) included in the cross-sectional 2002 WHO World Health Survey. Self-reported indicators of depression included: (a) its diagnosis, (b) its treatment, and (c) seven symptom items to determine presence of a major depressive episode. Similarly, information on AP comprised (a) a self-reported diagnosis, (b) self-reported AP treatment, (c) and a definition according to the WHO Rose questionnaire. In primary analyses, we operationalized depression or AP as positive if any of the respective indicators was present. Associations were estimated by multivariate logistic regression. In the entire sample (n = 213,264), the odds of AP were more than doubled among those with depression [odds ratio (OR) = 2.60, 95 % confidence interval = 2.36, 2.87] versus those without depression. These positive associations were replicated across all continents and were observed in both men and women. Likewise, meaningful associations (ORs ≥ 1.5) were observed in virtually all individual countries (46/47). Application of different operationalizations of depression and AP confirmed the above findings, both in the entire sample and in continent-specific analyses. Our study extends the current evidence accrued in Western populations to non-Western populations. The co-occurrence of AP and depression appears to represent a universal phenomenon. © 2014 Springer Science+Business Media.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Angina pectoris; Depression; Epidemiology; World Health Organization

The association of effort–reward imbalance and asthma: findings from two cross-sectional studies - Loerbroks, Adrian; Herr, Raphael M.; Li, Jian; Bosch, Jos A.; Seegel, Max; Schneider, Michael; Angerer, Peter; Schmidt, Burkhard (International Archives of Occupational and Environmental Health, 2015)
Purpose: There is evidence to suggest that work stress is positively associated with the occurrence of asthma. A limitation is that the small number of prior studies utilized unestablished work stress measures, thus constraining interpretation and generalizability. The present study re-examined this association by assessing work stress based on the well-established effort–reward imbalance (ERI) model. Methods: We drew on data from two cross-sectional studies. Study 1 was conducted in a large pharmaceutical company in 2013 (n = 1,464). Study 2 was based on data from the 2011 wave of the population-based German Socio-Economic Panel (n = 8,388). ERI was assessed by validated questionnaires. Asthma was determined by self-report of a physician-based diagnosis. Associations between ERI or its subcomponents “effort”, “reward” and “overcommitment” (z scores or categorized) with asthma were estimated by logistic regression models and reported as adjusted odds ratios (ORs) with 95 % confidence intervals (CIs). Results: A one standard deviation increase of the ERI score (reflecting higher work stress) was associated with a 22–48 % elevated odds of asthma (Study 1: OR 1.48, 95 % CI 1.13–1.95, and Study 2: OR 1.22, 95 % CI 1.10–1.36). Z score-based analyses of the separate ERI components generally suggested moderate associations of effort, reward and overcommitment with asthma in both studies (Study 1: OR effort 1.25, 95 % CI 0.95–1.64, OR reward 0.67, 95 % CI 0.51–0.87, OR overcommitment 1.32, 95 % CI 1.01–1.72; and Study 2: OR effort 1.21, 95 % CI 1.09–1.34, OR reward 0.83, 95 % CI 0.76–0.92, OR overcommitment 1.12, 95 % CI 1.01–1.25). Analyses of categorized exposures largely confirmed these observations. Conclusions: This is the first study to demonstrate a link between an established work stress measure and asthma. Longitudinal studies are needed to determine the direction of these associations.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Asthma; Effort–reward imbalance; Epidemiology; Germany; Work stress

The association of self-reported diabetes with impaired social functioning in low-, middle- and high-income countries: findings from the World Health Survey - Loerbroks, A.; Herr, Raphael M.; Icks, A.; Bosch, J. A. (Diabetic Medicine, 2018)
Aim: Epidemiological studies from high-income countries show that diabetes is associated with impaired social functioning. As healthcare systems in middle- and low-income countries offer fewer resources to curtail the potential social impact of diabetes, we performed a comparative study on the diabetes–social impairment link in low-, middle- and high-income countries. Methods: We use data from the cross-sectional World Health Survey (n = 235 428 from 10 low-income, 29 middle-income and 9 high-income countries). Diabetes was defined by self-reports of a diagnosis. Impaired social functioning was considered present if participants reported severe or extreme difficulties with personal relationships or participation in the community. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) in the overall sample and by income regions. ORs were corrected for demographics and health-related lifestyles, and then additionally adjusted for impairments that may explain any observed association (i.e. impaired vision, mood, cognition and mobility). Results: In the overall sample, we confirmed an association between self-reported diabetes and impaired social functioning (OR = 1.47, 95% CI = 1.18–1.83). The strength of that relationship increased with decreasing country income (e.g. OR in low-income countries = 2.23, 95% CI = 1.14–4.37). Associations were substantially attenuated by further correction for impairments, in particular mood problems, in the overall sample (OR = 0.92, 95% CI = 0.72–1.16) and all income regions. Conclusions: Self-reported diabetes is associated with impaired social functioning in high- and middle-income countries, and this relationship is even stronger in low-income countries. Associations are largely explained by physical and mental impairments, which may be due to diabetes.
CRIS-Team Scopus Importer:2022-11-28

The Benefits of an Employee-Friendly Company on Job Attitudes and Health of Employees: Findings from Matched Employer-Employee Data - Herr, Raphael; Brokmeier, Luisa; Fischer, Joachim E.; Mauss, Daniel (International Journal of Environmental Research and Public Health, 2022)
BACKGROUND: This study explored the association of an employee-friendly work environment with employees' job attitudes (engagement, commitment, turnover intentions, and job satisfaction), and health (mental and general health), applying matched employer-employee data. METHODS: The German Linked Personnel Panel (LPP; n = 14,182) survey simultaneously captures the data of employees and the human resources (HR) management of companies. A two-step cluster analysis of 16 items of the HR valuation identified relatively more- and less-employee-friendly companies (EFCs). Logistic regressions tested differences between these companies in the assessment of job attitudes and health of their employees. RESULTS: Compared to less-EFCS, more-EFCS had a reduced risk of poorer job attitudes and substandard health of their employees. For example, the risk for higher turnover intentions was reduced by 33% in more-EFCS (OR = 0.683, 95% C.I. = 0.626-0.723), and more-EFCS had an 18% reduced chance of poor mental health reporting of their employees (OR = 0.822, 95% C.I. = 0.758-0.892). CONCLUSIONS: More-EFCS have more motivated and healthier employees. The most distinct factors for more-EFCS were: the existence of development plans for employees, opportunities for advancement and development, and personnel development measures.
CRIS-Team Scopus Importer:2022-08-12
Keywords: company level; employee-friendly company; health; human resources (HR) management; job attitudes; matched employer–employee data

The longitudinal directional associations of meaningful work with mental well-being – initial findings from an exploratory investigation - Herr, Raphael; Brokmeier, Luisa; Baron, Bertil N.; Mauss, Daniel; Fischer, Joachim E. (BMC Psychology, 2023)
Background: An increasing number of studies reveal that more meaning in life is positively related to mental well-being. Meaning in life can be derived from different sources, including the workplace. The aim of this study was to explore the longitudinal directional association of meaningful work with mental well-being. Methods: Prospective data from 292 persons at two timepoints (two-week interval) were used to estimate the cross-lagged relationship and directionality of meaningful work with mental well-being. Results: The cross-lagged panel model had a good fit to the data (Chi2 ms(90) = 150.9; p < 0.001; RMSEA = 0.048; p = 0.576; CFI = 0.984; TLI = 0.979; SRMR = 0.040) and showed that levels of meaningful work at t1 had a positive effect on mental well-being at t2 (β = 0.15, p = 0.010). But mental well-being at t1 did not affect meaningful work at t2 (β = 0.02, p = 0.652). Sub-analyses revealed the effects to be mainly driven by women (as opposed to men) and white-collar workers (as opposed to blue-collar workers). Conclusion: This study confirmed a directional association of meaningful work on mental well-being, indicating that more meaningful work has beneficial mental well-being effects.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Cross-lagged model; Directional associations; Meaning in work; Meaningful work; Mental well-being; Purpose

The long-term impact of a change in Effort-Reward imbalance on mental health-results from the prospective MAN-GO study - Barrech, Amira; Riedel, Natalie; Li, Jian; Herr, Raphael M.; Moertl, Kathrin; Angerer, Peter; Guendel, Harald (European Journal of Public Health, 2017)
Background: Little is yet known on the long-term effects of stress management interventions (SMIs) in the workplace. The aim this study was to prospectively examine the effect of an improvement of psychosocial working conditions measured by the Effort-Reward (E-R) Imbalance model within 2 years following an SMI, and mental health 7 years later. Methods: The study sample consisted of 97 male industrial workers from southern Germany. Data were collected pre- and post-intervention in 2006 (T1) and 2008 (T2), respectively, as well as in 2015 (T3). Change scores were computed by subtracting T1 from T3 values. The associations between E-R ratio at T1, T2 and the change score, respectively, with depression and anxiety 7 years later were estimated by means of linear regression analysis. Analyses were adjusted for baseline levels of the exposure and outcome variables, socio-demographic-, health- and work-related covariates. Results: Within-person comparisons revealed a significant reduction (i.e. improvement) in E-R ratio post-intervention (-0.103, SD 0.24, P = 0.000). This improvement in the E-R ratio was significantly associated with lower anxiety (β = 0.358, P = 0.001) and depression (β = 0.246, P = 0.031) scores in the fully adjusted models. The association between change scores and mental health were slightly stronger than associations with absolute values at T1 and T2. Conclusions: An improvement in E-R ratio following an SMI, was significantly associated with lower anxiety and depression 7 years later. These results strongly support the importance of improving psychosocial working conditions in order to protect the mental health of employees in the long-run.
CRIS-Team Scopus Importer:2022-11-28

The relationship between ambivalence towards supervisor's behavior and employee’s mental health - Herr, Raphael M.; Birmingham, Wendy C.; Van Harreveld, Frenk; Van Vianen, Annelies E. M.; Fischer, Joachim E.; Bosch, Jos A. (Scientific Reports, 2022)
Ambivalence in social interactions has been linked to health-related outcomes in private relationships and recent research has started to expand this evidence to ambivalent leadership at the workplace by showing that ambivalent supervisor-employee relationships are related to higher stress levels in employees. However, the mental health consequences of ambivalent leadership have not been examined yet. Using a multilevel approach, this study estimated associations of ambivalent leadership with mental health indicators (depression, anxiety, vital exhaustion, fatigue) in 993 employees from 27 work groups. A total effect of ambivalent leadership was found for all four mental health measures, as well as within-group and between-group effects. The consistent relationships of ambivalent leadership with higher symptoms of mental ill-health at the individual- (i.e., within-group) and the group-level (i.e., between-group) support the existence of an un-confounded association, as well as group effects of collective ambivalence.
CRIS-Team Scopus Importer:2022-11-28

The Relationship of Ambivalence towards Lecturers with University Students’ Psychological Distress and Mental Health - Herr, Raphael; Birmingham, Wendy C.; Deyerl, Veronika; Diehl, Katharina (Social Sciences, 2024)
Social interactions that are simultaneously characterized by positive and negative aspects—i.e., ambivalent relationships—have been found to be related to distress and poor mental health. As the university setting is also characterized by several social interactions, this study aimed to investigate for the first time to what extent objective and subjective ambivalence towards lecturers or instructors are linked to university students’ distress levels and mental health indicators. A notable relationship of ambivalence with the outcomes was found in 1105 students from Germany. The association with psychological distress was more pronounced for objective than for subjective ambivalence (adjusted betas = 0.342 vs. 0.261, p-values < 0.001), while both also had an independent association. The association with mental health was comparable for both types (adjusted beta = −0.206 vs. −0.191, p-values < 0.001). For paradoxical emotions, the relationship with objective ambivalence was stronger, and only this remained significant in the mutually adjusted model (adjusted beta = 0.376, p-value < 0.001). This study provided evidence of a previously unconsidered stressor at the university—ambivalence towards lecturers—associated with negative health effects among students. Future studies are needed to establish this connection and to create the basis for preventative measures.
CRIS-Team Scopus Importer:2024-11-01
Keywords: ambivalence; ambivalent social relationships; distress; mental health; paradoxical emotions; university students

The Role of socio-economic Position and institutional Care Setting on Health of Kindergarten Children - Herr, Raphael M.; Mayer, A.; Wiedemann, E.; Diehl, Katharina; De Bock, F.; Blume, M.; Hoffmann, S.; Herke, M.; Reuter, M.; Iashchenko, I.; Schneider, S. (GESUNDHEITSWESEN, 2022)
CRIS-Team WoS Importer:2022-09-16

The roles of employment status and income in the mental health of informal caregivers in Germany - Scheuermann, Julia-Sophia; Pendergrass, Anna; Diehl, Katharina; Herr, Raphael (BMC Public Health, 2024)
Background: Informal caregivers often experience multiple negative consequences as a result of the informal care they provide. Among other factors, employment status, financial resources, and mental health are related to informal caregiving. This analysis examined the association between informal caregivers’ employment status and their mental health, as well as the moderating effect of net household income on this relationship. Methods: The research question was addressed with data from the German Socio-Economic Panel (SOEP) survey, comprising 3,053 informal caregivers (1,007 male; 2,046 female). Data were obtained through self-reports, and mental health was measured with the Summary Scale Mental Score. Stepwise adjusted multiple linear regression models were used to examine the association between employment status and mental health. The moderating effects were tested with interaction terms. All analyses were also stratified for gender. Results: Informal caregivers with full-time jobs reported better mental health than unemployed or marginally employed caregivers (β = 0.077, p < 0.001). The significant interaction term for full-time (β=-0.066, p = 0.001) and part-time workers (β=-0.066, p = 0.003) indicated a moderating effect of net household income on the association between employment status and mental health. This finding was especially evident in women. Conclusions: Employment appears to be a relevant protective factor for informal caregivers’ mental health. However, if informal caregivers are not employed, a low net household income might additionally restrict their mental health. Therefore, welfare policy structures must be created to reduce the negative financial consequences for informal caregivers and enable them to achieve work-life-care balance.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Employment; Informal caregiving; Mental health; Net household income

The synergistic effects of organizational justice and trust to supervisor on vagal tone: Preliminary findings of an empirical investigation - Herr, Raphael M.; Li, Jian; Angerer, Peter (International Journal of Environmental Research and Public Health, 2019)
The influence of perceived unfairness at the workplace (organizational injustice) on employee health is well established. Several theories explain the unpleasant and stressful nature of the experience of injustice, using trust as a central element. This study examines the effect of trust to supervisor on the association of perceived injustice with vagal tone—an objective marker for stress experience. Questionnaires assessed organizational justice and trust. Vagal tone was measured by indictors of heart rate variability (HRV), which captured parasympathetic (pNN50, RMSSD, and HF) and parasympathetic and sympathetic (SDNN, and LF) regulation. Synergistic effects were tested by linear regressions with interaction terms between organizational justice and trust to supervisor in 38 managers. Organizational justice was related to HRV indicators that reflect in particular the parasympathetic branch (β pNN50 = 0.32, p < 0.05; β RMSSD = 0.27, p < 0.1), and interaction effects with trust to supervisor were also most pronounced there (interaction β pNN50 = −0.41, p < 0.01; β RMSSD = −0.47, p < 0.01). In conclusion, the combination of low perceived justice and trust to supervisor appears substantial to the physiological stress threat of employees. Promoting fairness at the workplace might reduce stress; if not possible, trust to supervisor should be enhanced.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Heart rate variability; Organizational justice; Synergistic effects; Trust to supervisor; Vagal tone

The UFair-Questionnaire: Perceived university fairness and its association with mental health - Södel, Corinna; Herr, Raphael; Deyerl, Veronika; Diehl, Katharina (European Journal of Public Health, 2024)
Introduction University students face different stressors that might jeopardise their mental health. Hitherto, mainly general stress perceptions were assessed, which appeared inappropriate to indicate stress directly linked to the university or for deriving specific preventative measures. The aim of this study was to adapt the concept of organisational justice to universities, develop and validate a corresponding questionnaire (UFair: University Fairness Questionnaire), and estimate its association with mental health. Methods In total, 1,105 students (average age: 25.5 years [SD: 5.43]; female: 50.1%; university: 67.2%, university of applied sciences: 32.8%) were surveyed online. Perceived unfairness at the university was measured using the newly developed 20 item UFair Questionnaire. Mental health was measured using the Patient Health Questionnaire (PHQ-8, depression) and Maslach Burnout Inventory for Students (MBI-SS, burnout). Linear regression models estimated the adjusted (age, gender, type of university, lifestyle factors) relationship between perceived university injustice and mental health indicators. Results The UFair questionnaire showed good psychometric properties (Cronbach’s alpha = .960) and a unidimensional factor structure. There was a considerable association with depression (beta = .485; p < .001; R2 = .261) and burnout (beta = .481; p < .001; R2 = .250). Conclusions Perceived injustice represents not only a stressor at the workplace but also in the university setting, showing a considerable relationship with students’ mental health. University justice includes the perception of organisational aspects, the treatment of students, and consideration of the individual situation of students. The relevance of these aspects to the health of students should be recognised and taken into account by universities. The valid measurement by the UFair Questionnaire represents the basis for possible preventive approaches and interventions. Key messages • Organisational injustice exists not only in the workplace but also among students in the university setting. • Perceived unfairness among students is associated with depression and burnou
Keywords: depressive disorders; life style; mental healthorganizations; perception; psychometrics; workplace; gender; stress; stressor; burnout; linear regression; patient health questionnaire; prevention; college students

Three job stress models and their relationship with musculoskeletal pain in blue- and white-collar workers - Herr, Raphael M.; Bosch, Jos A.; Loerbroks, Adrian; Van Vianen, Annelies E. M.; Jarczok, Marc N.; Fischer, Joachim E.; Schmidt, Burkhard (Journal of Psychosomatic Research, 2015)
Objectives: Musculoskeletal pain has been found to co-occur with psychosocial job stress. However, different conceptualizations of job stress exist, each emphasizing different aspects of the work environment, and it is unknown which of these aspects show the strongest associations with musculoskeletal pain. Further, these associations may differ for white-collar vs. blue-collar job types, but this has not been tested. The present study examined the independent and combined contributions of Effort-RewardImbalance (ERI), Job-Demand-Control (JDC) and Organizational Justice (OJ) to musculoskeletal pain symptoms among white- and blue-collar workers. Methods: Participants of a cross-sectional study (n = 1634) completed validated questionnaires measuring ERI, JDC, and OJ, and reported the frequency of pain during the previous year at four anatomical locations (lower back, neck or shoulder, arms and hands, and knees/feet). Pain reports were summarized into a single musculoskeletal symptom score (MSS). Analyses were stratified for white- and blue-collar workers. Results: Among white-collar workers, ERI and OJ were independently associated with MSS. In addition to these additive effects, significant 2-way and 3-way interactions indicated a synergistic effect of job stressors in relation to reported pain. In blue-collar workers, ERI and JDC independently associated with MSS, and a significant 3-way interaction was observed showing that the combination of job stressors exceeded an additive effect. Conclusion: ERI influences pain symptoms in both occupational groups. OJ was independent significant predictor only among white-collar workers, whereas JDC had additive predictive utility exclusively among blue-collar workers. Simultaneous exposure to multiple job stress factors appeared to synergize pain symptom reporting.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Effort-reward imbalance; Job strain; Job-demand control; Musculoskeletal pain; Organizational justice; Work stress

Tonsillectomy with Uvulopalatopharyngoplasty in Obstructive Sleep Apnea - Sommer, J. Ulrich; Heiser, Clemens; Gahleitner, Constanze; Herr, Raphael M.; Hoermann, Karl; Maurer, Joachim T.; Stuck, Boris A. (Deutsches Ärzteblatt international, 2016)
CRIS-Team Scopus Importer:2022-11-28

Transformational leadership and depressive symptoms in Germany: Validation of a short transformational leadership scale - Seegel, Max Leonhard; Herr, Raphael M.; Schneider, Michael; Schmidt, Burkhard; Fischer, Joachim E. (Journal of Preventive Medicine and Public Health, 2019)
Objectives: The objective of the present study was to validate a shortened transformational leadership (TL) scale (12 items) comprising core TL behaviour and to test the associations of this shortened TL scale with depressive symptoms. Methods: The study used cross-sectional data from 1632 employees of the overall workforce of a middle-sized German company (51.6% men; mean age, 41.35 years; standard deviation, 9.4 years). TL was assessed with the German version of the Transformational Leadership Inventory and depressive symptoms with the Hospital Anxiety and Depression Scale (HADS). The structural validity of the core TL scale was assessed with confirmatory factor analysis. Associations with depressive symptoms were estimated with structural equation modelling and adjusted logistic regression. Results: Confirmatory factor analysis and structural equation modelling showed better model fit for the core TL than for the full TL score. Logistic regression revealed 3.61-fold (95% confidence interval [CI], 2.20 to 5.93: women) to 4.46-fold (95% CI, 2.86 to 6.95: men) increased odds of reporting depressive symptoms (HADS score >8) for those in the lowest tertile of reported core TL. Conclusions: The shortened core TL seems to be a valid instrument for research and training purposes in the context of TL and depressive symptoms in employees. Of particular note, men reporting poor TL were more likely to report depressive symptoms.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Depression; Germany; Leadership; Occupational health

Treatment preferences for biologicals in psoriasis: experienced patients appreciate sustainability - Kromer, Christian; Peitsch, Wiebke K.; Herr, Raphael M.; Schmieder, Astrid; Sonntag, Diana; Schaarschmidt, Marthe-Lisa (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Background and objectives: Treatment satisfaction can be improved by integrating patients’ preferences into shared decision-making. We recently investigated patients’ preferences for attributes of biologicals, and showed high preferences for safety and efficacy. The objective of the present study was to assess the impact of treatment experience on these preferences. Patients and methods: Preferences for outcome (probability of 50 % and 90 % improvement, time until response, sustainability of success, probability of mild and severe adverse events, probability of ACR 20 response) and process attributes (treatment location, frequency, duration, and delivery method) were analyzed in 200 participants with moderate-to-severe psoriasis using conjoint analysis. The impact of current and previous therapies, disease duration, and treatment satisfaction on ‘Relative Importance Scores’ was determined by analysis of variance, post hoc tests, and multivariate regression. Results: Participants presently on topical therapy (p = 0.02) or phototherapy (p = 0.032) placed more importance on treatment duration than others. Individuals who had previously been given traditional systemic agents (p = 0.028) or biologicals (p = 0.044) favored sustainability more than others. With an increasing number of systemic agents ever received (p = 0.045) and longer disease duration (p = 0.018), the latter attribute became increasingly important. Conclusions: Patients’ preferences for biologicals vary in correlation with treatment experience and disease duration, aspects to be addressed in the context of shared decision-making.
CRIS-Team Scopus Importer:2022-11-28

Treatment satisfaction of patients with psoriasis - Schaarschmidt, Marthe-Lisa; Kromer, Christian; Herr, Raphael M.; Schmieder, Astrid; Goerdt, Sergij; Peitsch, Wiebke K. (Acta Dermato-Venereologica, 2015)
Treatment satisfaction of patients with psoriasis largely depends on the treatment modality, but evidence on preferences for specific medications is scarce. Here we assessed treatment satisfaction of 200 participants with moderate-to-severe psoriasis from a German University hospital with a 5-point scale and the Treatment Satisfaction Questionnaire for Medication (TSQM) and determined sociodemographic and disease-related influence factors. Participants obtaining biologicals and traditional systemic medications were significantly more satisfied than those receiving phototherapy or topical agents (TSQM = 323.3, 288.0, 260.6 or 266.8; p < 0.001). The highest TSQM score was calculated for ustekinumab (350.1), followed by acitretin (338.1), adalimumab (323.0), fumaric acid esters (304.7), infliximab (300.2), etanercept (298.8), and methotrexate (272.3; p < 0.001). High disease-related quality of life impairment (β = –0.437, p < 0.001) and psoriatic arthritis (β = –0.185, p = 0.005) were associated with decreased satisfaction. Optimising satisfaction is essential to improve adherence and outcome. We show high preferences for biologicals, particularly ustekinumab, but also good satisfaction with certain traditional medications.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Biologicals; Preferences; Psoriasis; Systemic therapy; Treatment satisfaction; Ustekinumab

Trendprodukt E‑Zigarette: Einschätzung potenzieller Risiken durch Siebt- und Achtklässler - Schneider, Sven; Goerig, Tatiana; Herr, Raphael M.; Kreuter, Michael; Bauer-Kemeny, Claudia; Huerkamp, Robert; Diehl, Katharina (Prävention und Gesundheitsförderung, 2017)
Background: The electronic cigarette (e-cigarette) is an innovation which is rapidly gaining popularity around the world. Initial systematic reviews of the potential risks of e-cigarettes (nausea; dizziness; respiratory tract irritations; allergic reactions; brain and heart-circulation system damage; nicotine addiction and increased difficulty in quitting among cigarette smokers) have already been published. Aim: This paper is one of the first to investigate e-cigarette use and risk perception among adolescents. Study design: Between October 2014 and March 2015, 840 seventh- and eighth-grade school children from the Rhine-Neckar metropolitan region were anonymously interviewed. Results: Almost all of the school children questioned knew about e-cigarettes (98.0 %) and 16.2 % of those asked had used an e-cigarette at least once. The majority of the adolescents who had used e-cigarettes (namely 83 % of the e-cigarette users) did not smoke tobacco cigarettes. The majority of adolescents questioned perceived e-cigarettes which contain nicotine to be addictive (acceptance rating 88 %). Cluster analyses identified three different groups of adolescents with regard to risk perception: Those “generally concerned” (25 % of all adolescents questioned), those “concerned about long-term effects” (59 %), and those “generally unconcerned”(17 % of all adolescents questioned). The last cluster included a higher percentage of males, students from “Real-” and “Haupt-” (professional secondary) schools, and adolescents with migrant backgrounds. Implications: Analyses such as the one presented here make early monitoring possible and allow the development of data-based prevention measures.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Adolescent; Dependence potential; Electronic cigarette; Prevalence; Risk assessment

Trigeminal induced arousals during human sleep - Heiser, Clemens; Baja, Jan; Lenz, Franziska; Sommer, J. Ulrich; Hoermann, Karl; Herr, Raphael M.; Stuck, Boris A. (Sleep and Breathing, 2015)
Background: Arousals caused by external stimuli during human sleep have been studied for most of the sensorial systems. It could be shown that a pure nasal trigeminal stimulus leads to arousals during sleep. The frequency of arousals increases dependent on the stimulus concentration. The aim of the study was to evaluate the influence of different stimulus durations on arousal frequency during different sleep stages.Methods: Ten young healthy volunteers with 20 nights of polysomnography were included in the study. Pure trigeminal stimulation with both different concentrations of CO2 (0, 10, 20, 40 % v/v) and different stimulus durations (1, 3, 5, and 10 s) were applied during different sleep stages to the volunteers using an olfactometer. The application was performed during different sleep stages (light sleep, deep sleep, REM sleep).Results: The number of arousals increased with rising stimulus duration and stimulus concentration during each sleep stage.Conclusion: Trigeminal stimuli during sleep led to arousals in dose- and time-dependent manner.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Arousal latency; Chemosensation; Olfaction; Sleep; Trigeminal arousals

Type D personality and metabolic syndrome in a 7-year prospective occupational cohort - Mommersteeg, Paula M. C.; Herr, Raphael M.; Bosch, Jos; Fischer, Joachim E.; Loerbroks, Adrian (Journal of Psychosomatic Research, 2011)
Objective: Type D personality is a combination of high negative affectivity (NA) and high social inhibition (SI). This trait is related to increased mortality and poor health outcomes in patients with cardiovascular diseases, although it is less well-established if Type D personality also poses an increased risk in healthy populations. A potential underlying pathway could include the metabolic syndrome and the combination of abdominal obesity, subnormal levels of triglycerides and HDL-cholesterol, elevated blood pressure, and increased plasma glucose levels. We investigated if Type D personality shows a cross-sectional and longitudinal association with metabolic syndrome in a working population. Methods: Poisson regression and linear regression were used to estimate the association between Type D personality and its subscales (NA) and (SI) with objectively established metabolic syndrome markers in cross-sectional (n= 458) and prospective (n= 268, 6.3. years follow-up) analyses of data from an occupational cohort (mean age = 35.9. years, SD = 11.7; 80% male). Results: Type D personality was neither associated with the metabolic syndrome nor with any of its subcomponents. Conclusion: The present study does not support a role for metabolic syndrome as a mediating mechanism. More research is needed that examines potential pathways linking Type D personality with cardiovascular disease outcomes. © 2011 Elsevier Inc.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Cohort; Life style; Longitudinal; Metabolic syndrome; Occupational; Type D personality

Universitäre Gerechtigkeit und Gesundheitsoutcomes - Diehl, Katharina; Deyerl, Veronika; Herr, Raphael (Public Health Forum, 2024)
Perceptions of stress and the prevalence of mental illness are growing concerns among students. One source of stress may be perceived injustice in the university environment. The underlying concept of organizational justice is associated with various mental and physical health outcomes among employees. The aim of the present project is to transfer this concept, which is well established in work stress research, to students.
CRIS-Team Scopus Importer:2024-06-07
Keywords: injustice; mental health; stress; students; University

University Fairness Questionnaire (UFair): Development and Validation of a German Questionnaire to Assess University Justice—A Study Protocol of a Mixed Methods Study - Herr, Raphael; Deyerl, Veronika; Hilger-Kolb, Jennifer; Diehl, Katharina (International Journal of Environmental Research and Public Health, 2022)
Distress is a widespread phenomenon in the general population, but also among university students, associated with poorer learning success and negative health consequences. A source of distress might be the experience of injustice. Theoretical and empirical work in the area of perceived fairness in the workplace (“organizational justice”) has shown that perceived unfairness is related to various stress indicators and health outcomes. Preliminary evidence indicates that unfairness matters not only in the work context but also in the university context. However, an adapted and validated tool to assess perceived unfairness in the university context is hitherto missing. The goal of the proposed project is therefore to adapt the construct of organizational justice to the university context and to develop a corresponding questionnaire by means of established scientific procedures. An exploratory sequential mixed-methods design is applied in which qualitative and quantitative methods are combined. A valid and practicable measurement instrument (“UFair” University Fairness Questionnaire) will be developed and tested, and the relationship with various health outcomes will be examined. The UFair questionnaire will be made available free of charge to other researchers.
CRIS-Team Scopus Importer:2022-12-23
Keywords: development; fairness; health; justice; mixed-methods; questionnaire; stress; students; university; validation

Validating the Demand Control Support Questionnaire among white-collar employees in Switzerland and the United States - Mauss, Daniel; Herr, Raphael M.; Theorell, Tores; Angerer, Peter; Li, Jian (Journal of Occupational Medicine and Toxicology, 2018)
Background: The Demand Control Support Questionnaire (DCSQ) is an established self-reported tool to measure a stressful work environment. Validated German and English versions are however currently missing. The aim of this study was therefore to evaluate the psychometric properties of German and English versions of the DCSQ among white-collar employees in Switzerland and the US. Methods: This cross-sectional study was carried out on 499 employees in Switzerland and 411 in the US, respectively. The 17-item DCSQ with three scales assessed psychosocial stress at work (psychological demands, decision latitude, and social support at work). Depressive symptoms were measured by the 2-item Patient Health Questionnaire. Cronbach's α and item-total correlations tested the scale reliability (internal consistency). Construct validity of the questionnaire was examined using exploratory factor analysis (EFA). Logistic regressions estimated associations of each scale and job strain with depressive symptoms (criterion validity). Results: In both samples, all DCSQ scales presented satisfactory internal consistency (Cronbach's α ≥ 0.72; item-total correlations ≥ 0.33), and EFA showed the 17 items loading on three factors, which is in line with the theoretically assumed structure of the DCSQ construct. Moreover, all three scales as well as high job strain were significantly associated with depressive symptoms. The associations were stronger in the US sample. Conclusions: The German and the English versions of the DCSQ seem to be reliable and valid instruments to measure psychosocial stress based on the job demand-control-support model in the workplace of white-collar employees in Switzerland and the US.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Demand-control-support model; Depressive symptoms; Job strain; Psychosocial stress; Validation

Validating the short measure of the Effort-Reward Imbalance Questionnaire in older workers in the context of New Zealand - Li, Jian; Herr, Raphael M.; Allen, Joanne; Stephens, Christine; Alpass, Fiona (Journal of Occupational Health, 2017)
Objectives: The objective of this study was to validate a short version of the Effort-Reward-Imbalance (ERI) questionnaire in the context of New Zealand among older full-time and part-time employees. Methods: Data were collected from 1694 adults aged 48-83 years (mean 60 years, 53% female) who reported being in full- or part-time paid employment in the 2010 wave of the New Zealand Health, Work and Retirement study. Scale reliability was evaluated by item-total correlations and Cronbach's alpha. Factorial validity was assessed using multi-group confirmatory factor analyses assessing nested models of configural, metric, scalar and strict invariance across full- and part-time employment groups. Logistic regressions estimated associations of effortreward ratio and over-commitment with poor physical / mental health, and depressive symptoms. Results: Internal consistency of ERI scales was high across employment groups: effort 0.78-0.76; reward 0.81-0.77, and over-commitment 0.83-0.80. The three-factor model displayed acceptable fit in the overall sample (X2 / df = 10.31; CFI = 0.95; TLI = 0.94; RMSEA = 0.075), and decrements in model fit indices provided evidence for strict invariance of the three-factor ERI model across full-time and part-time employment groups. High effort-reward ratio scores were consistently associated with poor mental health and depressive symptoms for both employment groups. High overcommitment was associated with poor mental health and depressive symptoms in both groups and also with poor physical health in the full-time employment group. Conclusions: The short ERI questionnaire appears to be a valid instrument to assess adverse psychosocial work characteristics in old full-time and part-time employees in New Zealand.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Effort reward imbalance; Full-time and part-time employees; New Zealand; Older workers; Validation

Which meso-level characteristics of early childhood education and care centers are associated with health, health behavior, and well-being of young children? Findings of a scoping review - Herr, Raphael M.; Diehl, Katharina; Schneider, Sven; Osenbruegge, Nina; Memmer, Nicole; Sachse, Steffi; Hoffmann, Stephanie; Wachtler, Benjamin; Herke, Max; Pischke, Claudia R.; Novelli, Anna; Hilger-Kolb, Jennifer (International Journal of Environmental Research and Public Health, 2021)
Characteristics of early childhood education and care (ECEC) centers might be relevant for children’s health. This scoping review aims to provide an overview of the association between meso-level characteristics (MLCs) of ECEC centers with children’s health, health behavior, and wellbeing. Five databases were searched for quantitative and qualitative research articles published in English or German since 1 January 2000 on health, health behavior, and wellbeing of children aged 0 to 6 years considering MLCs of ECEC centers. Two authors screened 10,396 potentially eligible manuscripts and identified 117 papers, including 3077 examinations of the association between MLCs and children’s health indicators (Kappas > 0.91). Five categories of MLCs were identified: (1) structural characteristics, (2) equipment/furnishings, (3) location, (4) facilities/environment, (5) culture/activities/policies/practices, and 6) staff. Only very few studies found an association of MLCs with body weight/obesity, and general health and wellbeing. Especially physical activity and mental health were related to MLCs. In general, the location (rural vs. urban, neighborhood status) seemed to be a relevant health aspect. MLCs of ECEC centers appeared relevant for child health indicators to different degrees. Future research should focus on these associations, in detail, to identify concrete ECEC indicators that can support health promotion in early childhood.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Early childhood education and care (ECEC) centers; Health; Health behavior; Health inequalities; Kindergarten; Meso-level characteristics; Scoping review; Socioeconomic position; Young children

While You Are Sleeping: Marital Ambivalence and Blunted Nocturnal Blood Pressure - Birmingham, Wendy C.; Herr, Raphael; Cressman, Mikel; Patel, Neha; Hung, Man (International Journal of Environmental Research and Public Health, 2024)
Marital relationships offer health benefits, including a lower risk of cardiovascular disease (CVD). However, quality of the relationship matters; ambivalent behaviors may increase CVD risk by affecting blunted nocturnal blood pressure (BP) dipping. This study tracked daytime and nocturnal SBP and DBP in 180 normotensive individuals (90 couples; participant mean age 25.04; 91.58% white) over a 24 h period using ambulatory blood pressure monitors to explore the impact of martial quality. Results showed that perceptions of spousal ambivalence were associated with blunted nocturnal BP dipping. Perceptions of one’s own behavior as ambivalent also showed blunted nocturnal dipping. When in an ambivalent relationship, a gender interaction was found such that women were most likely to have blunted SBP dipping, but men were more likely to have blunted nocturnal DBP dipping. Overall, this study found an association between ambivalence and BP dipping, thus uncovering one virtually unexplored pathway by which marital relationships may have adverse effects on health.
CRIS-Team Scopus Importer:2024-07-12
Keywords: ambivalence; blood pressure; nocturnal dipping; relationship quality